Photosensitive resin composition, transfer film, cured film, laminate, and method for manufacturing touch panel

JP2025000704APending Publication Date: 2025-01-07FUJIFILM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024160253
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-10-11
Filing Date
2024-09-17
Publication Date
2025-01-07

AI Technical Summary

Benefits of technology

【0007】 本発明の一実施形態によれば、現像残渣抑制性、及び、得られる膜又は硬化膜の加熱処理後における膜周辺のむき出し配線の防錆性に優れる感光性樹脂組成物を提供することができる。 また、本発明の他の実施形態によれば、上記感光性樹脂組成物を用いた転写フィルム、硬化膜、積層体、及び、タッチパネルの製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000704000001_ABST
    Figure 2025000704000001_ABST
Patent Text Reader

Abstract

To provide a photosensitive resin composition that effectively inhibits development residues and prevents rust on an exposed wire around a film or a cured film obtained after heat treatment.SOLUTION: The present invention provides a photosensitive resin composition comprising a compound A that comprises a heterocyclic structure having at least one atom of an oxygen atom, a nitrogen atom, or a sulfur atom in a ring structure and at least one functional group selected from the group consisting of -SH, -OH, -COOH, -NH2 and-CONH2, an alkali-soluble binder polymer, an ethylenically unsaturated compound, and a photopolymerization initiator. The present invention also provides a transfer film, a cured film, a laminate, and a method for manufacturing a touch panel, using the photosensitive resin composition.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present disclosure relates to a photosensitive resin composition, a transfer film, a cured film, a laminate, and a method for manufacturing a touch panel. [Background technology]

[0002] In recent years, electronic devices such as mobile phones, car navigation systems, personal computers, ticket vending machines, and bank terminals have tablet-type input devices arranged on the surface of liquid crystal devices, etc. In such electronic devices, while referring to an instruction image displayed in the image display area of ​​the liquid crystal device, a user can input information corresponding to the instruction image by touching the area where the instruction image is displayed with a finger or a touch pen. The above-mentioned input devices (hereinafter also referred to as "touch panels") are classified into resistive film type, capacitance type, etc. The capacitance type input device has the advantage that it is only necessary to form a transparent conductive film on a single substrate. For example, one type of capacitance type input device has electrode patterns extending in mutually intersecting directions, and when a finger or the like comes into contact with the electrodes, the change in capacitance between the electrodes is detected to detect the input position. In a capacitance-type input device, a transparent resin layer is often provided for the purpose of protecting the electrode pattern, the wiring (e.g., metal wiring such as copper wire) gathered in the frame, etc. A photosensitive resin composition is often used as a material for forming such a transparent resin layer.

[0003] Furthermore, an example of a conventional surface-coated metal material is that described in Patent Document 1. Patent Document 1 describes a surface-coated metal material having, on at least one surface, a corrosion-resistant coating layer formed by dispersing at least a rust inhibitor in a matrix, and characterized in that the rust inhibitor comprises one or more organic compounds having a heterocyclic structure containing at least one element selected from nitrogen, sulfur, and oxygen, one or more functional groups containing at least one element selected from oxygen, nitrogen, and sulfur, and a structure having three or more sites capable of adsorbing metal elements. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2002-86613 Summary of the Invention [Problem to be solved by the invention]

[0005] The problem to be solved by one embodiment of the present invention is to provide a photosensitive resin composition that is excellent in suppressing development residues and in preventing rust on exposed wiring around the film after heat treatment of the resulting film or cured film. Another problem to be solved by another embodiment of the present invention is to provide a method for producing a transfer film, a cured film, a laminate, and a touch panel using the photosensitive resin composition. [Means for solving the problem]

[0006] The means for solving the above problems include the following aspects. <1> A photosensitive resin composition comprising: Compound A having a heterocyclic structure containing at least one atom selected from the group consisting of oxygen, nitrogen, and sulfur atoms within the ring structure, and at least one functional group selected from the group consisting of -SH, -OH, -COOH, -NH2, and -CONH2; an alkali-soluble binder polymer; an ethylenically unsaturated compound; and a photopolymerization initiator. <2> The compound A has, as the heterocyclic structure, a 5-membered heterocyclic ring having a nitrogen atom in the ring structure or a 6-membered heterocyclic ring having a nitrogen atom in the ring structure. <1> The photosensitive resin composition according to claim 1. <3> The compound A has a 6-membered heterocyclic ring having a nitrogen atom in the ring structure as the heterocyclic structure. <1> or <2> The photosensitive resin composition according to claim 1. <4> The heterocyclic structure in the compound A is a pyridine ring structure, a pyrimidine ring structure, or a 1,3,5-triazine ring structure. <1> ~ <3> 1. The photosensitive resin composition according to claim 1 . <5> The heterocyclic structure in the compound A is a pyridine ring structure. <1> ~ <4> 1. The photosensitive resin composition according to claim 1 . <6> The compound A is a compound having a total of 1 to 3 functional groups selected from the group consisting of -SH, -OH, -COOH, -NH2 and -CONH2. <1> ~ <5> 1. The photosensitive resin composition according to claim 1 . <7> The compound A is a compound having one functional group selected from the group consisting of -SH, -OH, -COOH, -NH2 and -CONH2. <1> ~ <6> 1. The photosensitive resin composition according to claim 1 . <8> The compound A is a compound having at least one functional group selected from the group consisting of -OH, -COOH, and -CONH2. <1> ~ <7> 1. The photosensitive resin composition according to claim 1 . <9> The compound A is a compound having one or two functional groups selected from the group consisting of -OH, -COOH, and -CONH2. <1> ~ <8> 1. The photosensitive resin composition according to claim 1 . <10> The compound A is a compound having one -COOH or -CONH2 as the functional group. <1> ~ <9> 1. The photosensitive resin composition according to claim 1 . <11> In the compound A, the functional group is a group directly bonded to a heterocyclic ring in the heterocyclic structure. <1> ~ <10> 1. The photosensitive resin composition according to claim 1 . <12> The content of the compound A is 0.1% by mass to 2.0% by mass based on the total solid content of the photosensitive resin composition. <1> ~ <11> 1. The photosensitive resin composition according to claim 1 . <13> The storage modulus of the photosensitive resin composition at 100°C is P × 10 2 Pa, the content of the compound A relative to the total solid content in the photosensitive resin composition is W A When expressed as mass%, the following formula 1 is satisfied: <1> ~ <12> 1. The photosensitive resin composition according to claim 1 . 0.01≦P / W A ≦1,000 Formula 1 <14> The storage modulus of the photosensitive resin composition at 100°C is P × 102 Pa, the content of the compound A relative to the total solid content in the photosensitive resin composition is W A When expressed as mass%, the following formula 2 is satisfied: <1> ~ <13> 1. The photosensitive resin composition according to claim 1 . 0.1≦P / W A ≦500 Formula 2 <15> A photosensitive resin composition for forming a protective film in a touch panel. <1> ~ <14> 1. The photosensitive resin composition according to claim 1 . <16> A temporary support; <1> ~ <15> a photosensitive layer formed from the photosensitive resin composition according to any one of the above items or formed by drying the photosensitive resin composition; <17> <1> ~ <15> 1. A cured film obtained by curing the photosensitive resin composition according to any one of 1 to 8. <18> a substrate, and <1> ~ <15> 1. A laminate having a cured film obtained by curing the photosensitive resin composition according to any one of 1 to 8. <19> A touch panel substrate having a surface on which at least one of a touch panel electrode and a touch panel wiring is arranged is prepared, and on the surface of the touch panel substrate on which at least one of the touch panel electrode and the touch panel wiring is arranged, <1> ~ <15> forming a photosensitive layer made of the photosensitive resin composition according to any one of the above items 1 to 4 or a photosensitive layer obtained by drying the photosensitive resin composition; pattern-exposing the photosensitive layer formed on the touch panel substrate; and developing the pattern-exposed photosensitive layer to obtain a protective film that protects at least a part of at least one of the touch panel electrodes and the touch panel wiring. [Effects of the Invention]

[0007] According to one embodiment of the present invention, it is possible to provide a photosensitive resin composition that is excellent in suppressing development residues and in preventing rust on exposed wiring around the film after heat treatment of the resulting film or cured film. According to another embodiment of the present invention, there can be provided a method for producing a transfer film, a cured film, a laminate, and a touch panel using the photosensitive resin composition. [Brief explanation of the drawings]

[0008] [Figure 1] 1 is a schematic cross-sectional view showing an example of a transfer film according to the present disclosure. [Figure 2] 1 is a schematic cross-sectional view showing a first specific example of a touch panel to which a photosensitive layer containing a photosensitive resin composition according to the present disclosure is applied. [Figure 3] FIG. 2 is a schematic cross-sectional view showing a second specific example of a touch panel to which a photosensitive layer containing the photosensitive resin composition according to the present disclosure is applied. DETAILED DESCRIPTION OF THE INVENTION

[0009] The present disclosure will be described in detail below. The following description of the components may be based on representative embodiments of the present disclosure, but the present disclosure is not limited to such embodiments. In the present disclosure, the use of "to" to indicate a range of values ​​means that the values ​​before and after it are included as the lower limit and upper limit. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of a numerical range may be replaced with a value shown in the examples. Furthermore, in the notation of groups (atomic groups) in the present disclosure, notations that do not specify whether they are substituted or unsubstituted include those that have a substituent as well as those that do not have a substituent. For example, the term "alkyl group" not only includes alkyl groups that do not have a substituent (unsubstituted alkyl groups) but also alkyl groups that have a substituent (substituted alkyl groups). In addition, in the present disclosure, "mass %" and "wt %" are synonymous, and "parts by mass" and "parts by weight" are synonymous. Furthermore, in the present disclosure, a combination of two or more preferred embodiments is a more preferred embodiment. In the present disclosure, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. In the present disclosure, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. In the present disclosure, "(meth)acrylic acid" is a concept that encompasses both acrylic acid and methacrylic acid, "(meth)acrylate" is a concept that encompasses both acrylate and methacrylate, and "(meth)acryloyl group" is a concept that encompasses both acryloyl group and methacryloyl group. Furthermore, unless otherwise specified, the weight-average molecular weight (Mw) and number-average molecular weight (Mn) in the present disclosure are molecular weights determined by gel permeation chromatography (GPC) using columns of TSKgel GMHxL, TSKgel G4000HxL, or TSKgel G2000HxL (all trade names manufactured by Tosoh Corporation), detection with a differential refractometer using THF (tetrahydrofuran) as a solvent, and conversion using polystyrene as a standard substance. In the present disclosure, unless otherwise specified, the molecular weight of a compound having a molecular weight distribution is the weight average molecular weight. In the present disclosure, unless otherwise specified, the ratio of polymer structural units is a molar ratio. In this disclosure, unless otherwise specified, the refractive index is a value measured at a wavelength of 550 nm using an ellipsometer at 25°C. The present disclosure will be described in detail below.

[0010] (Photosensitive resin composition) The photosensitive resin composition according to the present disclosure contains a compound A having a heterocyclic structure containing at least one atom selected from the group consisting of an oxygen atom, a nitrogen atom, and a sulfur atom within the ring structure and at least one functional group selected from the group consisting of -SH, -OH, -COOH, -NH2, and -CONH2; an alkali-soluble binder polymer; an ethylenically unsaturated compound; and a photopolymerization initiator. The photosensitive resin composition according to the present disclosure has excellent development residue suppression properties and excellent rust prevention properties for exposed wiring around the film after heat treatment of the resulting film or cured film (hereinafter simply referred to as "rust prevention properties"). Therefore, the photosensitive resin composition can be suitably used as a photosensitive resin composition for touch panels, can be more suitably used as a photosensitive resin composition for forming a protective film in a touch panel, and can be particularly suitably used as a photosensitive resin composition for forming an electrode protective film in a touch panel.

[0011] As a result of intensive research, the present inventors have found that the above-mentioned configuration makes it possible to provide a photosensitive resin composition that is excellent in suppressing development residues and in preventing rust on exposed wiring around the film after heat treatment of the resulting cured film. The mechanism of action of this excellent effect is not clear, but is presumed as follows. It is believed that the inclusion of Compound A, which has a heterocyclic structure containing at least one atom selected from the group consisting of oxygen, nitrogen, and sulfur atoms within the ring structure and at least one functional group selected from the group consisting of -SH, -OH, -COOH, -NH2, and -CONH2, causes Compound A to volatilize during heat treatment (also known as "baking") after film or cured film formation, preventing corrosion of exposed wiring (e.g., copper wiring) around the film or cured film, thereby providing excellent rust prevention. It is also believed that Compound A, which has a heterocyclic structure containing at least one atom selected from the group consisting of oxygen, nitrogen, and sulfur atoms within the ring structure and at least one functional group selected from the group consisting of -SH, -OH, -COOH, -NH2, and -CONH2, improves the adsorption of the heterocyclic structure and the functional group to wiring when they volatilize, resulting in excellent rust prevention. Furthermore, it is presumed that the compound A has at least one functional group selected from the group consisting of -SH, -OH, -COOH, -NH2 and -CONH2, which improves the solubility and dispersibility of development residues and also inhibits the aggregation of development residues, thereby making it possible to inhibit the generation of development residues.

[0012] <Compound A> The photosensitive resin composition according to the present disclosure contains a compound A having a heterocyclic structure containing at least one atom selected from the group consisting of oxygen, nitrogen, and sulfur atoms within the ring structure, and at least one functional group selected from the group consisting of -SH, -OH, -COOH, -NH2, and -CONH2. In Compound A, from the viewpoint of suppressing development residues and rust prevention, the functional group is preferably a group directly bonded to a heterocyclic ring in the heterocyclic structure.

[0013] From the viewpoint of suppressing development residues and rust prevention, the heterocyclic structure of compound A preferably has at least one atom of a nitrogen atom and a sulfur atom in the ring structure (also referred to as "having as a ring member" in the present disclosure), more preferably has a nitrogen atom in the ring structure, still more preferably has one or two nitrogen atoms in the ring structure, and particularly preferably has only one nitrogen atom in the ring structure. Furthermore, from the viewpoints of suppressing development residues and rust prevention, the heterocyclic structure of compound A is preferably a 5-membered heterocyclic structure or a 6-membered heterocyclic structure, and more preferably a 6-membered heterocyclic structure. Furthermore, from the viewpoints of suppressing development residues and rust prevention, Compound A preferably has a 5-membered heterocyclic structure having a nitrogen atom in the ring structure or a 6-membered heterocyclic structure having a nitrogen atom in the ring structure, and more preferably has a 6-membered heterocyclic structure having a nitrogen atom in the ring structure. The heterocyclic structure of compound A may be an aliphatic heterocyclic structure or an aromatic heterocyclic structure, or may be a monocyclic heterocyclic structure or a polycyclic structure in which at least one heterocycle is condensed. From the viewpoints of volatility and rust prevention, the heterocyclic structure is preferably an aromatic heterocyclic structure, and more preferably a monocyclic aromatic heterocyclic structure. Furthermore, compound A may have only one heterocyclic structure or two or more heterocyclic structures, and from the viewpoints of suppressing development residue, volatility, and rust prevention, it is preferable that compound A have only one heterocyclic structure.

[0014] Specific examples of the heterocyclic structure possessed by compound A include a pyridine ring structure, a pyrimidine ring structure, a 1,3,5-triazine ring structure, a pyrrole ring structure, a furan ring structure, a thiophene ring structure, an imidazole ring structure, a pyrazole ring structure, a triazole ring structure, a benzotriazole ring structure, a tetrazole ring structure, a thiadiazole ring structure, an oxazole ring structure, a thiazole ring structure, a benzothiazole ring structure, an indole ring structure, an isoindole ring structure, a benzimidazole ring structure, a benzoxazole ring structure, a quinoline ring structure, an isoquinoline ring structure, a phthalazine ring structure, a naphthyridine ring structure, a quinoxaline ring structure, a quinazoline ring structure, a cinnoline ring structure, a purine ring structure, a carbazole ring structure, a phenanthridine ring structure, and an acridine ring structure. Among these, from the viewpoints of suppressing development residue, volatility, and rust prevention, a pyridine ring structure, a pyrimidine ring structure, or a 1,3,5-triazine ring structure is preferred, and a pyridine ring structure is more preferred.

[0015] From the viewpoints of suppressing development residues, adsorption to wiring, and rust prevention, the functional group possessed by compound A is preferably at least one group selected from the group consisting of -SH, -OH, -COOH, and -CONH2, more preferably at least one group selected from the group consisting of -OH, -COOH, and -CONH2, even more preferably at least one group selected from the group consisting of -COOH and -CONH2, and particularly preferably -CONH2. From the viewpoint of suppressing development residues and rust prevention, compound A is preferably a compound having a total of 1 to 3 functional groups selected from the group consisting of -SH, -OH, -COOH, -NH2 and -CONH2, more preferably a compound having a total of 1 or 2 functional groups selected from the group consisting of -SH, -OH, -COOH, -NH2 and -CONH2, and particularly preferably a compound having one functional group selected from the group consisting of -SH, -OH, -COOH, -NH2 and -CONH2. Furthermore, from the viewpoints of suppressing development residue, adsorption to wiring, volatility, and rust prevention, compound A is preferably a compound having at least one of the functional groups selected from the group consisting of -OH, -COOH, and -CONH2, more preferably a compound having one or two of the functional groups selected from the group consisting of -OH, -COOH, and -CONH2, and particularly preferably a compound having one of the functional groups -COOH or -CONH2.

[0016] From the viewpoints of volatility and rust prevention, the molecular weight of compound A is preferably 500 or less, more preferably 80 or more and 300 or less, even more preferably 100 or more and 200 or less, and particularly preferably 100 or more and 150 or less.

[0017] From the viewpoint of suppressing development residue and rust prevention, compound A is preferably a compound represented by any one of the following formulas (A-1) to (A-3), and more preferably a compound represented by the following formula (A-1).

[0018] [ka]

[0019] In formulas (A-1) to (A-3), R a each independently represents -SH, -OH, -COOH, -NH2 or -CONH2; n1 represents an integer of 1 to 5; n2 represents an integer of 1 to 4; and n3 represents an integer of 1 to 3.

[0020] In formulas (A-1) to (A-3), R a From the viewpoints of suppressing development residue, adsorption to wiring, and rust prevention, is preferably -SH, -OH, -COOH, or -CONH2, more preferably -OH, -COOH, or -CONH2, even more preferably -COOH or -CONH2, and particularly preferably -CONH2. In formula (A-1), n1 is preferably an integer of 1 to 3, more preferably 1 or 2, and particularly preferably 1, from the viewpoints of suppression of development residue, adsorption to wiring, volatility, and rust prevention. In formula (A-2), n2 is preferably an integer of 1 to 3, more preferably 1 or 2, and particularly preferably 1, from the viewpoints of suppression of development residue, adsorption to wiring, volatility, and rust prevention. In formula (A-3), n3 is preferably 1 or 3, and more preferably 1, from the viewpoints of suppressing development residues and rust prevention.

[0021] Compound A is not particularly limited, and specific examples thereof include pyridine-2-carboxylic acid (picolinic acid), pyridine-3-carboxylic acid (nicotinic acid), pyridine-4-carboxylic acid (isonicotinic acid), 2-hydroxypyridine, 3-hydroxypyridine, 4-hydroxypyridine, 2-mercaptopyridine, 3-mercaptopyridine, 4-mercaptopyridine, 2-aminopyridine, 3-aminopyridine, 4-aminopyridine, pyridine-3,5-dicarboxylic acid, 2,3-dihydroxypyridine, pyridine-2-hydroxy-3-carboxylic acid, 2-aminopyrimidine, 4-hydroxypyrimidine, 2-pyrimidinethiol, and pyrimidine. 4-carboxylic acid, 4,6-dihydroxypyrimidine, 4-amino-6-hydroxypyrimidine, 4,5-diaminopyrimidine, 2,4-diamino-1,3,5-triazine, pyrazole-4-carboxylic acid, 5-benzotriazolecarboxylic acid, 2,6-dihydroxyisonicotinic acid, 2-amino-4,6-dihydroxypyrimidine, 2,4-diamino-6-hydroxypyrimidine, 4,6-diamino-2-mercaptopyrimidine, cyanuric acid (trihydroxytriazine), nicotinamide, 6-methylnicotinamide, isonicotinamide, 2-aminoisonicotinamide, 6-aminoisonicotinamide, and the like. Among these, from the viewpoints of suppressing development residues and rust prevention, Compound A is preferably at least one compound selected from the group consisting of pyridine-2-carboxylic acid, pyridine-3-carboxylic acid, 2-hydroxypyridine, 2-mercaptopyridine, 2-aminopyridine, 2,3-dihydroxypyridine, pyridine-2-hydroxy-3-carboxylic acid, 2-aminopyrimidine, 4-hydroxypyrimidine, pyrimidine-4-carboxylic acid, 4,6-dihydroxypyrimidine, pyrazole-4-carboxylic acid, 5-benzotriazolecarboxylic acid, 2,6-dihydroxyisonicotinic acid, cyanuric acid, nicotinamide, and isonicotinamide. More preferred is at least one compound selected from the group consisting of pyridine-2-carboxylic acid, pyridine-3-carboxylic acid, 2-hydroxypyridine, 2,3-dihydroxypyridine, pyridine-2-hydroxy-3-carboxylic acid, 4-hydroxypyrimidine, pyrimidine-4-carboxylic acid, 4,6-dihydroxypyrimidine, nicotinamide, and isonicotinamide, and particularly preferred is at least one compound selected from the group consisting of pyridine-2-carboxylic acid, pyridine-3-carboxylic acid, 2-hydroxypyridine, 2,3-dihydroxypyridine, pyridine-2-hydroxy-3-carboxylic acid, and isonicotinamide. Furthermore, from the viewpoint of versatility, nicotinamide, isonicotinamide, and pyridine-3-carboxylic acid are preferred as compound A. Furthermore, from the viewpoint of the balance between volatility and adsorption to wiring, at least one compound selected from the group consisting of isonicotinamide, pyridine-2-carboxylic acid, 2-hydroxypyridine, 2,3-dihydroxypyridine, pyridine-2-hydroxy-3-carboxylic acid, 4-hydroxypyrimidine, pyrimidine-4-carboxylic acid, and 4,6-dihydroxypyrimidine is preferred.

[0022] The compound A may be used alone or in combination of two or more kinds. From the viewpoints of suppressing development residues and rust prevention, the content of compound A is preferably 0.01% by mass to 20% by mass, more preferably 0.05% by mass to 10% by mass, even more preferably 0.1% by mass to 2.0% by mass, and particularly preferably 0.2% by mass to 1.8% by mass, relative to the total solid content in the photosensitive resin composition. The total solid content in the photosensitive resin composition in the present disclosure refers to the amount excluding volatile components such as solvents. Furthermore, the solid content in the present disclosure does not necessarily have to be solid, but may be liquid, or may be a mixture of solid and liquid.

[0023] The photosensitive resin composition according to the present disclosure has a storage modulus at 100°C of P × 10 2 Pa, the content of the compound A relative to the total solid content in the photosensitive resin composition is W A When expressed as mass %, it is preferable to satisfy the following formula 1, more preferable to satisfy the following formula 2, even more preferable to satisfy the following formula 3, and particularly preferable to satisfy the following formula 4. 0.01≦P / W A ≦1,000 Formula 1 0.1≦P / W A ≦500 Formula 2 0.5≦P / W A ≦10 Equation 3 0.5≦P / W A ≦4 Equation 4

[0024] In the present disclosure, the storage modulus of a photosensitive resin composition at 100° C. is measured by the following method. The storage modulus is measured using a rheometer (Discovery HR-2) manufactured by TA Instruments, Inc. A 20 mmφ parallel plate is used as a jig for fixing the sample. The photosensitive layer coating solution was applied onto a 16 μm thick polyethylene terephthalate film (temporary support, 16QS62 (16KS40) (Toray Industries, Inc.)) using a slit nozzle, adjusted so that the dried thickness would be 10 μm, and the photosensitive layer was formed by drying in a hot air convection dryer with a temperature gradient of 75°C to 120°C to remove the solvent. This was repeated 50 times to obtain a sample with a film thickness of approximately 500 μm. The prepared sample is placed between the plates and pressed tightly against the plates. Dynamic viscoelasticity is measured in shear mode, at a frequency of 1.0 Hz and a strain of 0.5%, in the temperature range of 20 to 125°C, at a heating rate of 5°C / min, to determine the storage modulus G' (Pa) at 100°C.

[0025] <Alkali-soluble binder polymer> The photosensitive resin composition according to the present disclosure contains an alkali-soluble binder polymer (hereinafter also simply referred to as "binder polymer"). In the present disclosure, "alkali-soluble" means that the solubility in 100 g of a 1% by mass aqueous solution of sodium carbonate at 22°C is 0.1 g or more. From the viewpoint of developability, the binder polymer is preferably a binder polymer having an acid value of 60 mgKOH / g or more. Furthermore, from the viewpoint that the binder polymer is easily thermally crosslinked with the crosslinking component by heating to form a strong film, it is more preferable that the binder polymer is a resin having a carboxy group with an acid value of 60 mgKOH / g or more (a so-called carboxy group-containing resin), and it is particularly preferable that the binder polymer is an acrylic resin having a carboxy group with an acid value of 60 mgKOH / g or more (a so-called carboxy group-containing acrylic resin). In the present disclosure, acrylic resin refers to a resin having a structural unit derived from a (meth)acrylic compound, and the content of the structural unit is preferably 30% by mass or more, and more preferably 50% by mass or more, relative to the total mass of the resin. When the binder polymer is a resin having a carboxy group, the three-dimensional crosslinking density can be increased by, for example, adding a thermally crosslinkable compound such as a blocked isocyanate compound to thermally crosslink the resin. Furthermore, when the carboxy group of the resin having a carboxy group is dehydrated and made hydrophobic, the wet heat resistance can be improved.

[0026] The carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more is not particularly limited as long as it satisfies the above-mentioned acid value condition, and can be appropriately selected from known acrylic resins. For example, among the polymers described in paragraph 0025 of JP-A No. 2011-95716, carboxyl group-containing acrylic resins having an acid value of 60 mgKOH / g or more, and among the polymers described in paragraphs 0033 to 0052 of JP-A No. 2010-237589, carboxyl group-containing acrylic resins having an acid value of 60 mgKOH / g or more can be preferably used.

[0027] From the viewpoints of suppressing development residues, the moisture permeability of the resulting cured film, and the adhesiveness of the resulting uncured film, the binder polymer is preferably an acrylic resin or a styrene-acrylic copolymer, and more preferably a styrene-acrylic copolymer. In the present disclosure, a styrene-acrylic copolymer refers to a resin having structural units derived from a styrene compound and structural units derived from a (meth)acrylic compound, and the total content of the structural units derived from the styrene compound and the structural units derived from the (meth)acrylic compound is preferably 30% by mass or more, and more preferably 50% by mass or more, relative to the total mass of the copolymer. Furthermore, the content of structural units derived from styrene compounds is preferably 1% by mass or more, more preferably 5% by mass or more, and particularly preferably 5% by mass or more and 80% by mass or less, relative to the total mass of the copolymer. Furthermore, the content of the structural units derived from the (meth)acrylic compound is preferably 5% by mass or more, more preferably 10% by mass or more, and particularly preferably 20% by mass or more and 95% by mass or less, relative to the total mass of the copolymer. Furthermore, the (meth)acrylic compound may include (meth)acrylate compounds, (meth)acrylic acid, (meth)acrylamide compounds, (meth)acrylonitrile, etc. Among these, at least one compound selected from the group consisting of (meth)acrylate compounds and (meth)acrylic acid is preferred.

[0028] -Structural units with aromatic rings- The binder polymer preferably contains a structural unit having an aromatic ring from the viewpoints of suppressing development residues and improving the moisture permeability and strength of the resulting cured film. Examples of the monomer that forms a structural unit having an aromatic ring include styrene compounds such as styrene, tert-butoxystyrene, methylstyrene, and α-methylstyrene, and benzyl (meth)acrylate. Of these, styrene compounds are preferred, with styrene being particularly preferred. Furthermore, from the viewpoint of moisture permeability and strength of the resulting cured film, the binder polymer more preferably has a structural unit represented by the following formula (S) (a structural unit derived from styrene).

[0029] [ka]

[0030] When the binder polymer contains a structural unit having an aromatic ring, the content of the structural unit having an aromatic ring is preferably 5% by mass to 90% by mass, more preferably 10% by mass to 70% by mass, and particularly preferably 20% by mass to 50% by mass, relative to the total mass of the binder polymer, from the viewpoints of moisture permeability and strength of the resulting cured film. Furthermore, from the viewpoint of moisture permeability and strength of the resulting cured film, the content of the structural unit having an aromatic ring in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and particularly preferably 20 mol % to 50 mol %, relative to the total amount of the binder polymer. Furthermore, from the viewpoint of moisture permeability and strength of the resulting cured film, the content of the structural unit represented by the above formula (S) in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and particularly preferably 20 mol % to 50 mol %, relative to the total amount of the binder polymer. In the present disclosure, when the content of a "structural unit" is specified by a molar ratio, the "structural unit" is considered to be synonymous with a "monomer unit." In addition, in the present disclosure, the "monomer unit" may be modified after polymerization by a polymer reaction or the like. The same applies hereinafter.

[0031] -Structural unit having an aliphatic hydrocarbon ring- The binder polymer preferably contains a structural unit having an aliphatic hydrocarbon ring from the viewpoints of suppressing development residues, the strength of the resulting cured film, and the adhesiveness of the resulting uncured film. Examples of the aliphatic hydrocarbon ring in the structural unit having an aliphatic hydrocarbon ring include a tricyclodecane ring, a cyclohexane ring, a cyclopentane ring, a norbornane ring, and an isoborone ring. Among these, from the viewpoints of the strength of the resulting cured film and the adhesiveness of the resulting uncured film, a ring in which two or more aliphatic hydrocarbon rings are condensed is preferred, and a tetrahydrodicyclopentadiene ring (tricyclo[5.2.1.0 2,6 ]decane ring) is particularly preferred. Examples of the monomer that forms a structural unit having an aliphatic hydrocarbon ring include dicyclopentanyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. Furthermore, from the viewpoint of the strength of the resulting cured film and the adhesiveness of the resulting uncured film, the binder polymer more preferably has a structural unit represented by the following formula (Cy), and particularly preferably has a structural unit represented by the above formula (S) and a structural unit represented by the following formula (Cy).

[0032] [ka]

[0033] In the formula (Cy), R M represents a hydrogen atom or a methyl group, and R Cy represents a monovalent group having an aliphatic hydrocarbon ring structure.

[0034] R in formula (Cy) M is preferably a methyl group. R in formula (Cy) Cy From the viewpoints of the strength of the resulting cured film and the adhesiveness of the resulting uncured film, is preferably a monovalent group having an aliphatic hydrocarbon ring structure with 5 to 20 carbon atoms, more preferably a monovalent group having an aliphatic hydrocarbon ring structure with 6 to 16 carbon atoms, and particularly preferably a monovalent group having an aliphatic hydrocarbon ring structure with 8 to 14 carbon atoms. Also, R in formula (Cy) Cy From the viewpoints of the strength of the resulting cured film and the adhesiveness of the resulting uncured film, the aliphatic hydrocarbon ring structure in is preferably a cyclopentane ring structure, a cyclohexane ring structure, a tetrahydrodicyclopentadiene ring structure, a norbornane ring structure, or an isoborone ring structure, more preferably a cyclohexane ring structure or a tetrahydrodicyclopentadiene ring structure, and particularly preferably a tetrahydrodicyclopentadiene ring structure. Furthermore, R in formula (Cy) Cy From the viewpoints of the strength of the resulting cured film and the adhesiveness of the resulting uncured film, the aliphatic hydrocarbon ring structure in is preferably a ring structure in which two or more aliphatic hydrocarbon rings are fused, and more preferably a ring in which two to four aliphatic hydrocarbon rings are fused. Furthermore, R in formula (Cy) Cy From the viewpoints of the strength of the resulting cured film and the adhesiveness of the resulting uncured film, is preferably a group in which the oxygen atom of —C(═O)O— in formula (Cy) is directly bonded to an aliphatic hydrocarbon ring structure, i.e., an aliphatic hydrocarbon ring group, more preferably a cyclohexyl group or a dicyclopentanyl group, and particularly preferably a dicyclopentanyl group.

[0035] The binder polymer may have one type of structural unit having an aliphatic hydrocarbon ring, or may have two or more types of structural units. When the binder polymer contains a structural unit having an aliphatic hydrocarbon ring, the content of the structural unit having an aliphatic hydrocarbon ring is preferably 5% by mass to 90% by mass, more preferably 10% by mass to 80% by mass, and particularly preferably 20% by mass to 70% by mass, relative to the total mass of the binder polymer, from the viewpoints of moisture permeability and strength of the resulting cured film. Furthermore, from the viewpoint of moisture permeability and strength of the resulting cured film, the content of the structural unit having an aliphatic hydrocarbon ring in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and particularly preferably 20 mol % to 50 mol %, relative to the total amount of the binder polymer. Furthermore, from the viewpoint of moisture permeability and strength of the resulting cured film, the content of the structural unit represented by the above formula (Cy) in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and particularly preferably 20 mol % to 50 mol %, relative to the total amount of the binder polymer.

[0036] When the binder polymer contains a structural unit having an aromatic ring and a structural unit having an aliphatic hydrocarbon ring, the total content of the structural unit having an aromatic ring and the structural unit having an aliphatic hydrocarbon ring is, from the viewpoint of the moisture permeability and strength of the resulting cured film, preferably from 10% to 90% by mass, more preferably from 20% to 80% by mass, and particularly preferably from 40% to 75% by mass, relative to the total mass of the binder polymer. Furthermore, from the viewpoint of the moisture permeability and strength of the resulting cured film, the total content of the aromatic ring-containing structural units and the aliphatic hydrocarbon ring-containing structural units in the binder polymer is preferably 10 mol % to 80 mol %, more preferably 20 mol % to 70 mol %, and particularly preferably 40 mol % to 60 mol %, relative to the total amount of the binder polymer. Furthermore, from the viewpoint of the moisture permeability and strength of the resulting cured film, the total content of the structural unit represented by the formula (S) and the structural unit represented by the formula (Cy) in the binder polymer is preferably 10 mol % to 80 mol %, more preferably 20 mol % to 70 mol %, and particularly preferably 40 mol % to 60 mol %, relative to the total amount of the binder polymer. Furthermore, from the viewpoint of the moisture permeability and strength of the obtained cured film, the molar amount nS of the constitutional unit represented by the above formula (S) and the molar amount nCy of the constitutional unit represented by the above formula (Cy) in the binder polymer preferably satisfy the relationship shown in the following formula (SCy), more preferably satisfy the following formula (SCy-1), and particularly preferably satisfy the following formula (SCy-2). 0.2≦nS / (nS+nCy)≦0.8 Formula (SCy) 0.30≦nS / (nS+nCy)≦0.75 Formula (SCy-1) 0.40≦nS / (nS+nCy)≦0.70 Formula (SCy-2)

[0037] -Structural unit having an acid group- The binder polymer preferably contains a structural unit having an acid group from the viewpoints of suppressing development residues, strength of the resulting cured film, and developability. Examples of the acid group include a carboxy group, a sulfo group, a phosphonic acid group, and a phosphoric acid group, with the carboxy group being preferred. Preferred examples of the structural unit having an acid group include structural units derived from (meth)acrylic acid, as shown below, and more preferred examples include structural units derived from methacrylic acid.

[0038] [ka]

[0039] The binder polymer may have one type of structural unit having an acid group, or two or more types of structural units having an acid group. When the binder polymer contains a structural unit having an acid group, the content of the structural unit having an acid group is preferably 5% by mass to 50% by mass, more preferably 5% by mass to 40% by mass, and particularly preferably 10% by mass to 30% by mass, relative to the total mass of the binder polymer, from the viewpoints of the strength of the obtained cured film and developability. Furthermore, from the viewpoints of the strength of the resulting cured film and developability, the content of the structural unit having an acid group in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 50 mol %, and particularly preferably 20 mol % to 40 mol %, relative to the total amount of the binder polymer. Furthermore, from the viewpoints of the strength of the resulting cured film and developability, the content of the structural units derived from (meth)acrylic acid in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 50 mol %, and particularly preferably 20 mol % to 40 mol %, relative to the total amount of the binder polymer.

[0040] -Structural unit having a reactive group- From the viewpoint of the strength of the resulting cured film and the adhesiveness of the resulting uncured film, the binder polymer preferably has a reactive group, and more preferably has a structural unit having a reactive group. The reactive group is preferably a radically polymerizable group, more preferably an ethylenically unsaturated group. When the binder polymer has an ethylenically unsaturated group, the binder polymer preferably has a structural unit having an ethylenically unsaturated group in a side chain. In the present disclosure, the term "main chain" refers to the relatively longest bond chain in the molecule of the polymer compound that constitutes the resin, and the term "side chain" refers to an atomic group branching off from the main chain. The ethylenically unsaturated group is preferably a (meth)acrylic group, more preferably a (meth)acryloxy group. Examples of structural units having a reactive group include, but are not limited to, those shown below.

[0041] [ka]

[0042] The binder polymer may have one type of structural unit having a reactive group, or may have two or more types of structural units. When the binder polymer contains a structural unit having a reactive group, the content of the structural unit having a reactive group is preferably 5% by mass to 70% by mass, more preferably 10% by mass to 50% by mass, and particularly preferably 20% by mass to 40% by mass, relative to the total mass of the binder polymer, from the viewpoints of the strength of the resulting cured film and the adhesiveness of the resulting uncured film. Furthermore, from the viewpoints of the strength of the resulting cured film and the adhesiveness of the resulting uncured film, the content of the structural unit having a reactive group in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and particularly preferably 20 mol % to 50 mol %, relative to the total amount of the binder polymer.

[0043] Examples of a means for introducing a reactive group into a binder polymer include a method of reacting a hydroxy group, a carboxy group, a primary amino group, a secondary amino group, an acetoacetyl group, a sulfo group, or the like with an epoxy compound, a blocked isocyanate compound, an isocyanate compound, a vinyl sulfone compound, an aldehyde compound, a methylol compound, a carboxylic acid anhydride, or the like. A preferred example of a method for introducing a reactive group into a binder polymer is to synthesize a polymer having a carboxy group by polymerization, and then react some of the carboxy groups of the resulting polymer with glycidyl (meth)acrylate by a polymer reaction to introduce a (meth)acryloxy group into the polymer. By this method, a binder polymer having a (meth)acryloxy group in the side chain can be obtained. The polymerization reaction is preferably carried out at a temperature of 70°C to 100°C, and more preferably at a temperature of 80°C to 90°C. The polymerization initiator used in the polymerization reaction is preferably an azo-based initiator, and more preferably, for example, V-601 (trade name) or V-65 (trade name) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. The polymerization reaction is preferably carried out at a temperature of 80°C to 110°C. In the polymerization reaction, it is preferable to use a catalyst such as an ammonium salt.

[0044] As the binder polymer, from the viewpoint of suppressing development residue, the following polymers are preferred: The content ratios (a to d) of the following structural units and the weight average molecular weight Mw can be changed as appropriate depending on the purpose.

[0045] [ka]

[0046] [ka]

[0047] The binder polymer may also contain a polymer containing a structural unit having a carboxylic acid anhydride structure (hereinafter also referred to as "polymer B"). When the photosensitive resin composition contains polymer B, it is possible to improve the developability and strength after curing. The carboxylic acid anhydride structure may be either a chain carboxylic acid anhydride structure or a cyclic carboxylic acid anhydride structure, but is preferably a cyclic carboxylic acid anhydride structure. The ring of the cyclic carboxylic acid anhydride structure is preferably a 5- to 7-membered ring, more preferably a 5- or 6-membered ring, and particularly preferably a 5-membered ring.

[0048] The structural unit having a carboxylic acid anhydride structure is preferably a structural unit containing, in the main chain, a divalent group obtained by removing two hydrogen atoms from a compound represented by the following formula P-1, or a structural unit in which a monovalent group obtained by removing one hydrogen atom from a compound represented by the following formula P-1 is bonded to the main chain directly or via a divalent linking group.

[0049] [ka]

[0050] In formula P-1, R A1a represents a substituent, n 1a R A1a may be the same or different, and Z 1a represents a divalent group forming a ring containing -C(=O)-OC(=O)-, and n 1a represents an integer greater than or equal to 0.

[0051] R A1a Examples of the substituent represented by the formula include an alkyl group. Z 1a As the alkylene group, an alkylene group having 2 to 4 carbon atoms is preferred, an alkylene group having 2 or 3 carbon atoms is more preferred, and an alkylene group having 2 carbon atoms is particularly preferred. n 1a represents an integer greater than or equal to 0. 1a When represents an alkylene group having 2 to 4 carbon atoms, n 1a is preferably an integer of 0 to 4, more preferably an integer of 0 to 2, and particularly preferably 0. n 1a If represents an integer of 2 or more, there are multiple R A1a may be the same or different. A1a may be bonded to each other to form a ring, but preferably do not bond to each other to form a ring.

[0052] The structural unit having a carboxylic acid anhydride structure is preferably a structural unit derived from an unsaturated carboxylic acid anhydride, more preferably a structural unit derived from an unsaturated cyclic carboxylic acid anhydride, even more preferably a structural unit derived from an unsaturated aliphatic cyclic carboxylic acid anhydride, particularly preferably a structural unit derived from maleic anhydride or itaconic anhydride, and most preferably a structural unit derived from maleic anhydride.

[0053] Specific examples of structural units having a carboxylic acid anhydride structure are listed below, but the structural units having a carboxylic acid anhydride structure are not limited to these specific examples. In the following structural units, Rx represents a hydrogen atom, a methyl group, a CH2OH group, or a CF3 group, and Me represents a methyl group.

[0054] [ka]

[0055] [ka]

[0056] The structural unit having a carboxylic acid anhydride structure in the polymer B may be of one type alone, or may be of two or more types.

[0057] The total content of structural units having a carboxylic acid anhydride structure relative to the total amount of polymer B is preferably 0 mol % to 60 mol %, more preferably 5 mol % to 40 mol %, and particularly preferably 10 mol % to 35 mol %.

[0058] The photosensitive resin composition according to the present disclosure may contain only one type of polymer B, or may contain two or more types. When the photosensitive resin composition according to the present disclosure contains polymer B, the content of polymer B is preferably 0.1% by mass to 30% by mass, more preferably 0.2% by mass to 20% by mass, even more preferably 0.5% by mass to 20% by mass, and particularly preferably 1% by mass to 20% by mass, relative to the total solid content of the photosensitive resin composition, from the viewpoints of photocurability, developability, and strength of the resulting cured film.

[0059] From the viewpoints of the strength of the resulting cured film and the adhesiveness of the resulting uncured film, the weight average molecular weight (Mw) of the binder polymer is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 10,000 to 50,000, even more preferably 15,000 to 30,000, and particularly preferably 20,000 to 30,000.

[0060] The acid value of the binder polymer is preferably 10 mgKOH / g to 200 mgKOH / g, more preferably 60 mgKOH / g to 200 mgKOH / g, further preferably 60 mgKOH / g to 150 mgKOH / g, and particularly preferably 60 mgKOH / g to 110 mgKOH / g. The acid value of the binder polymer is a value measured according to the method described in JIS K0070:1992.

[0061] The photosensitive resin composition according to the present disclosure may contain only one type of binder polymer, or may contain two or more types of binder polymers. The content of the binder polymer is preferably 10% by mass to 90% by mass, more preferably 20% by mass to 80% by mass, and even more preferably 30% by mass to 70% by mass, relative to the total solid content of the photosensitive resin composition, from the viewpoints of, for example, the strength of the cured film and the handleability of the transfer film. In the binder polymer, the content of the residual monomer of each structural unit is preferably 5,000 ppm by mass or less, more preferably 2,000 ppm by mass or less, and even more preferably 500 ppm by mass or less, based on the total mass of the binder polymer containing that structural unit, from the viewpoints of patterning ability and reliability. Although there is no particular lower limit, it is preferably 1 ppm by mass or more, and more preferably 10 ppm by mass or more. From the viewpoints of patterning ability and reliability, the residual monomer content of each structural unit of the binder polymer is preferably 3,000 ppm by mass or less, more preferably 600 ppm by mass or less, and even more preferably 100 ppm by mass or less, relative to the photosensitive layer described below. There is no particular lower limit, but it is preferably 0.1 ppm by mass or more, more preferably 1 ppm by mass or more. It is also preferable that the amount of residual monomers in the binder polymer synthesis by a polymer reaction be within the above range. For example, when the binder polymer is synthesized by reacting glycidyl acrylate with a carboxylic acid side chain, it is preferable that the content of glycidyl acrylate be within the above range.

[0062] <Ethylenically unsaturated compounds> The photosensitive resin composition according to the present disclosure contains an ethylenically unsaturated compound. In the photosensitive resin composition according to the present disclosure, the ethylenically unsaturated compound contributes to photosensitivity (i.e., photocurability) and strength of the cured film. Furthermore, the ethylenically unsaturated compound in the present disclosure is a compound other than the above-mentioned binder polymer, and preferably has a molecular weight of less than 5,000. Furthermore, among these, from the viewpoints of substrate adhesion, suppression of development residue, and rust prevention, the photosensitive resin composition according to the present disclosure preferably contains, as the ethylenically unsaturated compound, a compound represented by formula (M) described below and an ethylenically unsaturated compound having an acid group, more preferably 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, and a polyfunctional ethylenically unsaturated compound having a carboxylic acid group, and particularly preferably 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, and a succinic acid-modified product of dipentaerythritol pentaacrylate. Furthermore, from the viewpoints of the strength of the obtained cured film, substrate adhesion, suppression of development residues, and rust prevention, the photosensitive resin composition according to the present disclosure preferably contains, as the ethylenically unsaturated compound, a compound represented by formula (M) described later, an ethylenically unsaturated compound having an acid group, and a thermally crosslinkable compound described later, and more preferably contains a compound represented by formula (M) described later, an ethylenically unsaturated compound having an acid group, and a blocked isocyanate compound described later.

[0063] From the viewpoints of suppressing development residues, rust prevention, and bending resistance of the resulting cured film, the ethylenically unsaturated compound preferably contains a compound represented by the following formula (M) (also simply referred to as "compound M"). Q 2 -R 1 -Q 1 Formula (M) In formula (M), Q 1 and Q 2 each independently represents a (meth)acryloyloxy group, R 1 represents a divalent linking group having a chain structure.

[0064] Q in formula (M) 1 and Q 2 From the viewpoint of ease of synthesis, Q 1 and Q 2 are preferably the same group. Also, Q in formula (M) 1 and Q 2is preferably an acryloyloxy group from the viewpoint of reactivity. R in formula (M) 1 From the viewpoint of the bending resistance of the resulting cured film, the alkylene group, the alkyleneoxyalkylene group (-L 1 -OL 1 -), or a polyalkyleneoxyalkylene group (-(L 1 -O) p -L 1 -), more preferably a hydrocarbon group having 2 to 20 carbon atoms or a polyalkyleneoxyalkylene group, still more preferably an alkylene group having 4 to 20 carbon atoms, and particularly preferably a straight-chain alkylene group having 6 to 18 carbon atoms. The hydrocarbon group may have a chain structure at least in part, and the portion other than the chain structure is not particularly limited and may be, for example, a branched, cyclic, or straight-chain alkylene group having 1 to 5 carbon atoms, an arylene group, an ether bond, or a combination thereof. From the viewpoint of the bending resistance of the resulting cured film, the alkylene group or a group combining two or more alkylene groups and one or more arylene groups is preferred, an alkylene group is more preferred, and a straight-chain alkylene group is particularly preferred. In addition, the above L 1 each independently represents an alkylene group, preferably an ethylene group, a propylene group, or a butylene group, and more preferably an ethylene group or a 1,2-propylene group. p represents an integer of 2 or more, preferably an integer of 2 to 10.

[0065] Also, Q in compound M 1 and Q 2 The number of atoms in the shortest linking chain connecting the and is preferably 3 to 50, more preferably 4 to 40, even more preferably 6 to 20, and particularly preferably 8 to 12, from the viewpoint of the moisture permeability and bending resistance of the resulting cured film. In this disclosure, "Q 1 and Q 2 The number of atoms in the shortest chain connecting the 1 Connect to R1 Q from atoms in 2 Connect to R 1 is the shortest number of atoms that connects to the atom in

[0066] Specific examples of the compound M include 1,3-butanediol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,7-heptanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,4-cyclohexanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, di(meth)acrylate of hydrogenated bisphenol A, di(meth)acrylate of hydrogenated bisphenol F, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, poly(ethylene glycol / propylene glycol) di(meth)acrylate, and polybutylene glycol di(meth)acrylate. The above ester monomers may also be used as a mixture. Among the above compounds, from the viewpoint of the bending resistance of the resulting cured film, at least one compound selected from the group consisting of 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate is preferred, at least one compound selected from the group consisting of 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and 1,10-decanediol di(meth)acrylate is more preferred, and at least one compound selected from the group consisting of 1,9-nonanediol di(meth)acrylate and 1,10-decanediol di(meth)acrylate is particularly preferred.

[0067] The compound M may be used alone or in combination of two or more kinds. From the viewpoint of moisture permeability and bending resistance of the resulting cured film, the content of compound M is preferably 10% by mass to 90% by mass, more preferably 15% by mass to 70% by mass, even more preferably 20% by mass to 50% by mass, and particularly preferably 25% by mass to 35% by mass, relative to the total mass of the ethylenically unsaturated compounds in the photosensitive resin composition. In the present disclosure, the ethylenically unsaturated compound refers to a compound having an ethylenically unsaturated group and a (weight average) molecular weight of 10,000 or less. Furthermore, from the viewpoint of moisture permeability and bending resistance of the resulting cured film, the content of compound M is preferably 1% by mass to 30% by mass, more preferably 3% by mass to 25% by mass, even more preferably 5% by mass to 20% by mass, and particularly preferably 6% by mass to 14.5% by mass, relative to the total solid content in the photosensitive resin composition. In the present disclosure, the total solid content in the photosensitive resin composition refers to the amount excluding volatile components such as solvents.

[0068] The ethylenically unsaturated compound preferably contains a di- or higher functional ethylenically unsaturated compound. In the present disclosure, the term "difunctional or higher functional ethylenically unsaturated compound" refers to a compound having two or more ethylenically unsaturated groups in one molecule. The ethylenically unsaturated group in the ethylenically unsaturated compound is preferably a (meth)acryloyl group. As the ethylenically unsaturated compound, a (meth)acrylate compound is preferred.

[0069] From the viewpoint of the strength of the cured film after curing, it is particularly preferable that the ethylenically unsaturated compound contains a bifunctional ethylenically unsaturated compound (preferably a bifunctional (meth)acrylate compound) and a trifunctional or higher ethylenically unsaturated compound (preferably a trifunctional or higher (meth)acrylate compound).

[0070] The difunctional ethylenically unsaturated compound is not particularly limited and can be appropriately selected from known compounds. Examples of the difunctional ethylenically unsaturated compound other than the compound M include tricyclodecane dimethanol di(meth)acrylate and tricyclodecane dimenanol di(meth)acrylate.

[0071] Commercially available bifunctional ethylenically unsaturated compounds include tricyclodecane dimethanol diacrylate (trade name: NK Ester A-DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimenanol dimethacrylate (trade name: NK Ester DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), 1,9-nonanediol diacrylate (trade name: NK Ester A-NOD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.), and 1,6-hexanediol diacrylate (trade name: NK Ester A-HD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.).

[0072] The tri- or higher functional ethylenically unsaturated compound is not particularly limited and can be appropriately selected from known compounds. Examples of tri- or higher functional ethylenically unsaturated compounds include dipentaerythritol (tri / tetra / penta / hexa)(meth)acrylate, pentaerythritol (tri / tetra)(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, isocyanuric acid (meth)acrylate, and (meth)acrylate compounds having a glycerin tri(meth)acrylate skeleton.

[0073] Here, "(tri / tetra / penta / hexa)(meth)acrylate" is a concept that encompasses tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate, and hexa(meth)acrylate, and "(tri / tetra)(meth)acrylate" is a concept that encompasses tri(meth)acrylate and tetra(meth)acrylate.

[0074] Examples of the ethylenically unsaturated compound include caprolactone-modified (meth)acrylate compounds (KAYARAD (registered trademark) DPCA-20 manufactured by Nippon Kayaku Co., Ltd., A-9300-1CL manufactured by Shin-Nakamura Chemical Co., Ltd., etc.), alkylene oxide-modified (meth)acrylate compounds (KAYARAD (registered trademark) RP-1040 manufactured by Nippon Kayaku Co., Ltd., ATM-35E and A-9300 manufactured by Shin-Nakamura Chemical Co., Ltd., EBECRYL (registered trademark) 135 manufactured by Daicel-Allnex Corporation, etc.), and ethoxylated glycerin triacrylate (NK Ester A-GLY-9E manufactured by Shin-Nakamura Chemical Co., Ltd., etc.).

[0075] Examples of the ethylenically unsaturated compound include urethane (meth)acrylate compounds (preferably tri- or higher functional urethane (meth)acrylate compounds), such as propylene oxide-modified urethane di(meth)acrylate and ethylene oxide and propylene oxide-modified urethane di(meth)acrylate. The tri- or higher functional urethane (meth)acrylate compound preferably has six or more functional groups, and more preferably has eight or more functional groups. The upper limit of the number of functional groups can be, for example, 20 or less. Commercially available products include 8UX-015A (manufactured by Taisei Fine Chemical Co., Ltd.), NK Ester UA-32P (manufactured by Shin-Nakamura Chemical Co., Ltd.), U-15HA (manufactured by Shin-Nakamura Chemical Co., Ltd.), NK Ester UA-1100H (manufactured by Shin-Nakamura Chemical Co., Ltd.), UA-306H, UA-306T, UA-306I, UA-510H, and UX-5000 (all manufactured by Nippon Kayaku Co., Ltd.).

[0076] The ethylenically unsaturated compound preferably contains an ethylenically unsaturated compound having an acid group, from the viewpoints of developability and suppression of development residues. Examples of the acid group include a phosphate group, a sulfo group, and a carboxy group. Of these, the acid group is preferably a carboxy group. Examples of the ethylenically unsaturated compound having an acid group include trifunctional to tetrafunctional ethylenically unsaturated compounds having an acid group [those in which a carboxy group has been introduced into a pentaerythritol tri- and tetraacrylate (PETA) skeleton (acid value: 80 mg KOH / g to 120 mg KOH / g)], and pentafunctional to hexafunctional ethylenically unsaturated compounds having an acid group [those in which a carboxy group has been introduced into a dipentaerythritol penta- and hexaacrylate (DPHA) skeleton (acid value: 25 mg KOH / g to 70 mg KOH / g)]. These tri- or higher functional ethylenically unsaturated compounds having an acid group may be used in combination with a difunctional ethylenically unsaturated compound having an acid group, if necessary.

[0077] The ethylenically unsaturated compound having an acid group is preferably at least one selected from the group consisting of di- or higher functional ethylenically unsaturated compounds having a carboxy group and carboxylic acid anhydrides thereof. When the ethylenically unsaturated compound having an acid group is at least one selected from the group consisting of di- or higher functional ethylenically unsaturated compounds having a carboxy group and carboxylic acid anhydrides thereof, the developability and film strength are further improved. The di- or higher functional ethylenically unsaturated compound having a carboxy group is not particularly limited and can be appropriately selected from known compounds. As the difunctional or higher ethylenically unsaturated compound having a carboxy group, Aronix (registered trademark) TO-2349 (manufactured by Toagosei Co., Ltd.), Aronix (registered trademark) M-520 (manufactured by Toagosei Co., Ltd.), Aronix (registered trademark) M-510 (manufactured by Toagosei Co., Ltd.), etc. can be preferably used.

[0078] As the ethylenically unsaturated compound having an acid group, the polymerizable compounds having an acid group described in paragraphs 0025 to 0030 of JP-A No. 2004-239942 can be preferably used, and the contents of this publication are incorporated herein by reference.

[0079] The photosensitive resin composition according to the present disclosure may contain one type of ethylenically unsaturated compound having an acid group, or may contain two or more types of ethylenically unsaturated compounds having an acid group. From the viewpoints of developability and the adhesiveness of the resulting uncured film, the content of the ethylenically unsaturated compound having an acid group is preferably 0.1% by mass to 30% by mass, more preferably 0.5% by mass to 20% by mass, even more preferably 1% by mass to 10% by mass, and particularly preferably 1% by mass to 5% by mass, relative to the total solid content of the photosensitive resin composition.

[0080] Furthermore, from the viewpoints of the moisture permeability and bending resistance of the resulting cured film and the adhesiveness of the resulting uncured film, the ethylenically unsaturated compound preferably contains a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, more preferably contains a bifunctional ethylenically unsaturated compound having a ring structure in which two or more aliphatic hydrocarbon rings are condensed, and particularly preferably contains tricyclodecane dimethanol di(meth)acrylate. From the viewpoints of the moisture permeability and bending resistance of the resulting cured film and the adhesiveness of the resulting uncured film, the aliphatic hydrocarbon ring structure is preferably a cyclopentane ring structure, a cyclohexane ring structure, a tricyclodecane ring structure, a norbornane ring structure, or an isoborone ring structure, more preferably a cyclohexane ring structure or a tricyclodecane ring structure, and particularly preferably a tricyclodecane ring structure. Furthermore, from the viewpoints of the moisture permeability and bending resistance of the resulting cured film and the adhesiveness of the resulting uncured film, the photosensitive resin composition according to the present disclosure preferably contains a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure and a binder polymer having a structural unit having an aliphatic hydrocarbon ring.

[0081] The photosensitive resin composition according to the present disclosure may contain one type of bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, or may contain two or more types of bifunctional ethylenically unsaturated compounds. From the viewpoints of the moisture permeability and bending resistance of the resulting cured film and the adhesiveness of the resulting uncured film, the content of the bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure is preferably 1% by mass to 50% by mass, more preferably 5% by mass to 40% by mass, even more preferably 10% by mass to 30% by mass, and particularly preferably 15% by mass to 25% by mass, relative to the total solid content of the photosensitive resin composition.

[0082] From the viewpoint of rust prevention, the ethylenically unsaturated compound preferably contains a compound M and a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure. Furthermore, from the viewpoints of substrate adhesion, suppression of development residues, and rust prevention, the ethylenically unsaturated compound preferably contains compound M and an ethylenically unsaturated compound having an acid group, more preferably contains compound M, a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, and an ethylenically unsaturated compound having an acid group, still more preferably contains compound M, a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, a tri- or higher functional ethylenically unsaturated compound, and an ethylenically unsaturated compound having an acid group, and particularly preferably contains compound M, a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, a tri- or higher functional ethylenically unsaturated compound, an ethylenically unsaturated compound having an acid group, and a urethane (meth)acrylate compound. Furthermore, from the viewpoints of substrate adhesion, suppression of development residue, and rust prevention, the ethylenically unsaturated compound preferably includes 1,9-nonanediol diacrylate and a polyfunctional ethylenically unsaturated compound having a carboxylic acid group, preferably includes 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, and a polyfunctional ethylenically unsaturated compound having a carboxylic acid group, more preferably includes 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, dipentaerythritol hexaacrylate, and an ethylenically unsaturated compound having a carboxylic acid group, and particularly preferably includes 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, an ethylenically unsaturated compound having a carboxylic acid group, and a urethane acrylate compound.

[0083] The photosensitive resin composition according to the present disclosure may contain a monofunctional ethylenically unsaturated compound as the ethylenically unsaturated compound. The content of the difunctional or higher functional ethylenically unsaturated compound in the ethylenically unsaturated compound is preferably 60% by mass to 100% by mass, more preferably 80% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass, based on the total content of all ethylenically unsaturated compounds contained in the photosensitive resin composition.

[0084] The molecular weight of the ethylenically unsaturated compound is preferably 200 to 3,000, more preferably 250 to 2,600, even more preferably 280 to 2,200, and particularly preferably 300 to 2,200. Among the ethylenically unsaturated compounds contained in the photosensitive resin composition according to the present disclosure, the content of ethylenically unsaturated compounds having a molecular weight of 300 or less is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less, based on the content of all ethylenically unsaturated compounds contained in the photosensitive resin composition.

[0085] The photosensitive resin composition according to the present disclosure may contain only one type of ethylenically unsaturated compound, or may contain two or more types. The content of the ethylenically unsaturated compound in the photosensitive resin composition according to the present disclosure is preferably 1% by mass to 70% by mass, more preferably 10% by mass to 70% by mass, even more preferably 20% by mass to 60% by mass, and particularly preferably 20% by mass to 50% by mass, relative to the total solid content of the photosensitive resin composition.

[0086] <Photopolymerization initiator> The photosensitive resin composition according to the present disclosure contains a photopolymerization initiator. The photopolymerization initiator is not particularly limited, and known photopolymerization initiators can be used. Examples of the photopolymerization initiator include a photopolymerization initiator having an oxime ester structure (hereinafter also referred to as an "oxime-based photopolymerization initiator"), a photopolymerization initiator having an α-aminoalkylphenone structure (hereinafter also referred to as an "α-aminoalkylphenone-based photopolymerization initiator"), a photopolymerization initiator having an α-hydroxyalkylphenone structure (hereinafter also referred to as an "α-hydroxyalkylphenone-based polymerization initiator"), a photopolymerization initiator having an acylphosphine oxide structure (hereinafter also referred to as an "acylphosphine oxide-based photopolymerization initiator"), and a photopolymerization initiator having an N-phenylglycine structure (hereinafter also referred to as an "N-phenylglycine-based photopolymerization initiator").

[0087] The photopolymerization initiator preferably contains at least one selected from the group consisting of oxime-based photopolymerization initiators, α-aminoalkylphenone-based photopolymerization initiators, α-hydroxyalkylphenone-based polymerization initiators, and N-phenylglycine-based photopolymerization initiators, and more preferably contains at least one selected from the group consisting of oxime-based photopolymerization initiators, α-aminoalkylphenone-based photopolymerization initiators, and N-phenylglycine-based photopolymerization initiators. Furthermore, from the viewpoints of substrate adhesion, suppression of development residues, and rust prevention, it is preferable to use two or more types of photopolymerization initiators in combination, and it is more preferable to include an oxime-based photopolymerization initiator and an α-aminoalkylphenone-based photopolymerization initiator, and it is particularly preferable to include 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyloxime) and 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one.

[0088] Furthermore, as the photopolymerization initiator, for example, polymerization initiators described in paragraphs 0031 to 0042 of JP-A No. 2011-95716 and paragraphs 0064 to 0081 of JP-A No. 2015-014783 may be used.

[0089] Commercially available photopolymerization initiators include 1-[4-(phenylthio)phenyl]-1,2-octanedione-2-(O-benzoyloxime) [trade name: IRGACURE® OXE-01, manufactured by BASF], 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyloxime) [trade name: IRGACURE® OXE-02, manufactured by BASF], and [8-[5-(2,4,6-trimethylphenyl)-11-(2-ethylhexyl)-11H-benzo[a]carbazolyl][2-(2,2,3,3-tetrafluoropropoxy)phenyl]methanone-(O-acetyloxime) [trade name: IRGACURE® OXE-03, manufactured by BASF], 1-[4-[4-(2-benzofuranylcarbonyl)phenyl]thio]phenyl]-4-methylpentanone-1-(O-acetyloxime) [trade name: IRGACURE® OXE-04, manufactured by BASF], 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone [trade name: IRGACURE® 379EG, manufactured by BASF], 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one [trade name: IRGACURE® 907, manufactured by BASF], 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one [trade name: IRGACURE® 127, manufactured by BASF), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1 (trade name: IRGACURE® 369, manufactured by BASF), 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: IRGACURE® 1173, manufactured by BASF), 1-hydroxycyclohexyl phenyl ketone (trade name: IRGACURE® 184, manufactured by BASF), 2,2-dimethoxy-1,2-diphenylethan-1-one (trade name: IRGACURE 651, manufactured by BASF), and other oxime esters (trade name: Lunar® 6, manufactured by DKSH Japan Co., Ltd.), 1-[4-(phenylthio)phenyl]-3-cyclopentylpropane-1,Examples include 2-dione-2-(O-benzoyloxime) (trade name: TR-PBG-305, manufactured by Changzhou Powerful Electronic New Materials Co., Ltd.), 1,2-propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furanylcarbonyl)-9H-carbazol-3-yl]-, 2-(O-acetyloxime) (trade name: TR-PBG-326, manufactured by Changzhou Powerful Electronic New Materials Co., Ltd.), and 3-cyclohexyl-1-(6-(2-(benzoyloxyimino)hexanoyl)-9-ethyl-9H-carbazol-3-yl)-propane-1,2-dione-2-(O-benzoyloxime) (trade name: TR-PBG-391, manufactured by Changzhou Powerful Electronic New Materials Co., Ltd.).

[0090] The photosensitive resin composition according to the present disclosure may contain only one type of photopolymerization initiator, or may contain two or more types of photopolymerization initiators. The content of the photopolymerization initiator in the photosensitive resin composition according to the present disclosure is not particularly limited, but is preferably 0.1 mass % or more, more preferably 0.5 mass % or more, and even more preferably 1.0 mass % or more, relative to the total solid content of the photosensitive resin composition. The content of the photopolymerization initiator in the photosensitive resin composition according to the present disclosure is preferably 10% by mass or less, and more preferably 5% by mass or less, based on the total solid content of the photosensitive resin composition.

[0091] <Thermal crosslinkable compound> The photosensitive resin composition according to the present disclosure preferably contains a thermally crosslinkable compound from the viewpoints of the strength of the cured film obtained and the adhesiveness of the uncured film obtained. Note that, in the present disclosure, a thermally crosslinkable compound having an ethylenically unsaturated group, which will be described later, is not treated as an ethylenically unsaturated compound but as a thermally crosslinkable compound. Examples of the thermally crosslinkable compound include an epoxy compound, an oxetane compound, a methylol compound, a blocked isocyanate compound, etc. Among these, blocked isocyanate compounds are preferred from the viewpoints of the strength of the resulting cured film and the adhesiveness of the resulting uncured film. The blocked isocyanate compound reacts with a hydroxy group and a carboxy group. Therefore, for example, when at least one of the binder polymer and the radically polymerizable compound having an ethylenically unsaturated group has at least one of a hydroxy group and a carboxy group, the hydrophilicity of the formed film tends to decrease and the function as a protective film tends to be enhanced. The blocked isocyanate compound refers to a compound having a structure in which the isocyanate group of an isocyanate is protected (so-called masked) with a blocking agent.

[0092] The dissociation temperature of the blocked isocyanate compound is not particularly limited, but is preferably 100°C to 160°C, and more preferably 130°C to 150°C. In the present disclosure, the dissociation temperature of a blocked isocyanate means "the temperature of the endothermic peak accompanying the deprotection reaction of the blocked isocyanate when measured by DSC (Differential Scanning Calorimetry) analysis using a differential scanning calorimeter." As the differential scanning calorimeter, for example, a differential scanning calorimeter (model: DSC6200) manufactured by Seiko Instruments Inc. can be suitably used, but the differential scanning calorimeter is not limited to this.

[0093] Examples of blocking agents having a dissociation temperature of 100°C to 160°C include active methylene compounds (such as malonic acid diesters (dimethyl malonate, diethyl malonate, di-n-butyl malonate, di-2-ethylhexyl malonate, etc.)), and oxime compounds (compounds having a structure represented by -C(=N-OH)- in the molecule, such as formaldoxime, acetaldoxime, acetoxime, methylethylketoxime, and cyclohexanoneoxime). Among these, as the blocking agent having a dissociation temperature of 100° C. to 160° C., at least one selected from oxime compounds is preferred from the viewpoint of storage stability, for example.

[0094] The blocked isocyanate compound preferably has an isocyanurate structure, for example, from the viewpoint of improving the brittleness of the film and improving the adhesive strength to the transfer target. A blocked isocyanate compound having an isocyanurate structure can be obtained, for example, by protecting hexamethylene diisocyanate by isocyanuration. Among blocked isocyanate compounds having an isocyanurate structure, compounds having an oxime structure in which an oxime compound is used as a blocking agent are preferred from the viewpoints that the dissociation temperature can be more easily adjusted to a preferred range and development residues can be reduced compared to compounds not having an oxime structure.

[0095] The blocked isocyanate compound may have a polymerizable group. The polymerizable group is not particularly limited, and any known polymerizable group can be used, with a radical polymerizable group being preferred. Examples of the polymerizable group include an ethylenically unsaturated group such as a (meth)acryloxy group, a (meth)acrylamide group, or a styryl group, and a group having an epoxy group such as a glycidyl group. Among these, from the viewpoints of the surface state of the resulting cured film, the development rate, and the reactivity, the polymerizable group is preferably an ethylenically unsaturated group, more preferably a (meth)acryloxy group, and particularly preferably an acryloxy group.

[0096] As the blocked isocyanate compound, commercially available products can be used. Examples of commercially available blocked isocyanate compounds include Karenz (registered trademark) AOI-BM, Karenz (registered trademark) MOI-BM, Karenz (registered trademark) MOI-BP, and the like (all manufactured by Showa Denko K.K.), and the blocked Duranate series (e.g., Duranate (registered trademark) TPA-B80E, Duranate (registered trademark) WT32-B75P, and the like, manufactured by Asahi Kasei Chemicals Corporation).

[0097] The photosensitive resin composition according to the present disclosure may contain only one type of thermally crosslinkable compound, or may contain two or more types. When the photosensitive resin composition according to the present disclosure contains a thermally crosslinkable compound, the content of the thermally crosslinkable compound is preferably 1% by mass to 50% by mass, and more preferably 5% by mass to 30% by mass, relative to the total solid content of the photosensitive resin composition.

[0098] <Aliphatic thiol compounds> The photosensitive resin composition according to the present disclosure preferably contains an aliphatic thiol compound other than the compound A. When the photosensitive resin composition according to the present disclosure contains an aliphatic thiol compound, the aliphatic thiol compound undergoes an ene-thiol reaction, which suppresses the cure shrinkage of the film formed and relieves stress, and therefore tends to improve the adhesion of the cured film formed to the substrate (particularly, the adhesion after exposure). Generally, when a photosensitive resin composition contains an aliphatic thiol compound, metals (particularly copper) are more likely to corrode. In contrast, the photosensitive resin composition according to the present disclosure has the advantage that it can form a cured film that has excellent corrosion inhibition properties for metals (particularly copper), even when it contains an aliphatic thiol compound.

[0099] As the aliphatic thiol compound, a monofunctional aliphatic thiol compound or a polyfunctional aliphatic thiol compound (that is, a di- or higher functional aliphatic thiol compound) is suitably used. Among these, the aliphatic thiol compound preferably contains a polyfunctional aliphatic thiol compound, and more preferably is a polyfunctional aliphatic thiol compound, from the viewpoint of, for example, the adhesion of the cured film to the substrate (particularly, the adhesion after exposure). In the present disclosure, the term "polyfunctional aliphatic thiol compound" refers to an aliphatic compound having two or more thiol groups (also called "mercapto groups") in the molecule. The polyfunctional aliphatic thiol compound is preferably a low molecular weight compound having a molecular weight of at least 100. Specifically, the molecular weight of the polyfunctional aliphatic thiol compound is more preferably 100 to 1,500, and even more preferably 150 to 1,000.

[0100] The number of functional groups in the polyfunctional aliphatic thiol compound is preferably 2 to 10, more preferably 2 to 8, and even more preferably 2 to 6, from the viewpoint of, for example, the adhesion of the formed cured film to the substrate.

[0101] Examples of polyfunctional aliphatic thiol compounds include trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetrakis(3-mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), and tetraethylene glycol bicarbonate. Examples of suitable mercaptothiol include bis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), ethylene glycol bisthiopropionate, 1,4-bis(3-mercaptobutyryloxy)butane, 1,2-ethanedithiol, 1,3-propanedithiol, 1,6-hexamethylenedithiol, 2,2'-(ethylenedithio)diethanethiol, meso-2,3-dimercaptosuccinic acid, and di(mercaptoethyl)ether.

[0102] Among these, the polyfunctional aliphatic thiol compound is preferably at least one selected from the group consisting of trimethylolpropane tris(3-mercaptobutyrate) and 1,4-bis(3-mercaptobutyryloxy)butane.

[0103] Examples of monofunctional aliphatic thiol compounds include 1-octanethiol, 1-dodecanethiol, β-mercaptopropionic acid, methyl-3-mercaptopropionate, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, and stearyl-3-mercaptopropionate.

[0104] The photosensitive resin composition according to the present disclosure may contain only one type of aliphatic thiol compound, or may contain two or more types. When the photosensitive resin composition according to the present disclosure contains an aliphatic thiol compound, the content of the aliphatic thiol compound is preferably 5% by mass or more, more preferably 5% by mass to 50% by mass, even more preferably 5% by mass to 30% by mass, and particularly preferably 8% by mass to 20% by mass, relative to the total solid content of the photosensitive resin composition. When the content of the aliphatic thiol compound is 5% by mass or more relative to the total solid content of the photosensitive resin composition, a cured film having excellent adhesion (particularly, adhesion after exposure) to a substrate (particularly, a copper substrate) tends to be formed.

[0105] <Surfactant> The photosensitive resin composition according to the present disclosure may contain a surfactant. The surfactant is not particularly limited, and any known surfactant can be used. Examples of the surfactant include those described in paragraph 0017 of Japanese Patent No. 4502784 and paragraphs 0060 to 0071 of JP-A No. 2009-237362.

[0106] As the surfactant, a fluorine-based surfactant or a silicon-based surfactant (also called a "silicone-based surfactant") is preferred. Commercially available fluorine-based surfactants include, for example, Megafac F-171, F-172, F-173, F-176, F-177, F-141, F-142, F-143, F-144, F-437, F-475, F-477, F-479, F-482, F-551-A, F-552, F-554, F-555-A, F-556, F-557, F-558, F-559, and F-5 60, F-561, F-565, F-563, F-568, F-575, F-780, EXP, MFS-330, R-41, R-41-LM, R-01, R-40, R-40-LM, RS-43, TF-1956, RS-90, R-94, RS-72-K, DS-21 (all manufactured by DIC Corporation), Fluorad Examples of such a binder include FC430, FC431, and FC171 (manufactured by Sumitomo 3M Limited), Surflon S-382, SC-101, SC-103, SC-104, SC-105, SC-1068, SC-381, SC-383, S-393, and KH-40 (manufactured by AGC Inc.), PolyFox PF636, PF656, PF6320, PF6520, and PF7002 (manufactured by OMNOVA), and Ftergent 710FM, 610FM, 601AD, 601ADH2, 602A, 215M, and 245F (manufactured by NEOS Corporation). In addition, acrylic compounds that have a molecular structure with a functional group containing a fluorine atom and that volatilize when heated by cleavage of the fluorine atom-containing functional group can also be used as fluorosurfactants. Examples of such fluorosurfactants include the Megafac DS series manufactured by DIC Corporation (The Chemical Daily, February 22, 2016; The Nikkei Business Daily, February 23, 2016), such as Megafac DS-21. It is also preferable to use, as the fluorine-based surfactant, a polymer of a fluorine atom-containing vinyl ether compound having a fluorinated alkyl group or a fluorinated alkylene ether group and a hydrophilic vinyl ether compound. The fluorine-based surfactant may also be a block polymer. As the fluorine-based surfactant, a fluorine-containing polymer compound containing a repeating unit derived from a (meth)acrylate compound having a fluorine atom and a repeating unit derived from a (meth)acrylate compound having two or more (preferably five or more) alkyleneoxy groups (preferably ethyleneoxy groups or propyleneoxy groups) may also be preferably used. The fluorine-based surfactant may also be a fluorine-containing polymer having an ethylenically unsaturated bond-containing group in the side chain, such as Megafac RS-101, RS-102, RS-718K, or RS-72-K (all manufactured by DIC Corporation). Examples of nonionic surfactants include glycerol, trimethylolpropane, trimethylolethane, and their ethoxylates and propoxylates (for example, glycerol propoxylate, glycerol ethoxylate, etc.), polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyethylene glycol dilaurate, polyethylene glycol distearate, sorbitan fatty acid esters, Pluronic L10, L31, L61, L62, 10R5, 17R2, 25R2 (all manufactured by BASF), Tetronic 304, 701, 704, 901, 904, 150R1 (all manufactured by BASF), and Solsperse 20000 (all manufactured by Lubrizol Nippon Co., Ltd.), NCW-101, NCW-1001, NCW-1002 (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), Paionin D-6112, D-6112-W, D-6315 (all manufactured by Takemoto Oil & Fat Co., Ltd.), Olfine E1010, Surfynol 104, 400, 440 (all manufactured by Nissin Chemical Industry Co., Ltd.), and the like. Examples of commercially available silicon-based surfactants include linear polymers consisting of siloxane bonds and modified siloxane polymers in which organic groups have been introduced into the side chains or terminals. Specific examples of surfactants include DOWSIL 8032 ADDITIVE, Toray Silicone DC3PA, Toray Silicone SH7PA, Toray Silicone DC11PA, Toray Silicone SH21PA, Toray Silicone SH28PA, Toray Silicone SH29PA, Toray Silicone SH30PA, and Toray Silicone SH8400 (all manufactured by Toray Dow Corning Co., Ltd.), as well as X-22-4952, X-22-4272, X-22-6266, KF-351A, K354L, KF-355A, and KF- 945, KF-640, KF-642, KF-643, X-22-6191, X-22-4515, KF-6004, KP-341, KF-6001, KF-6002 (all manufactured by Shin-Etsu Silicones Co., Ltd.), F-4440, TSF-4300, TSF-4445, TSF-4460, TSF-4452 (all manufactured by Momentive Performance Materials), BYK307, BYK323, BYK330 (all manufactured by BYK-Chemie), and the like.

[0107] The photosensitive resin composition according to the present disclosure may contain only one type of surfactant, or may contain two or more types of surfactants. When the photosensitive resin composition according to the present disclosure contains a surfactant, the content of the surfactant is preferably 0.01% by mass to 3.0% by mass, more preferably 0.05% by mass to 1% by mass, and even more preferably 0.1% by mass to 0.8% by mass, relative to the total solid content of the photosensitive resin composition.

[0108] <Hydrogen donor compounds> The photosensitive resin composition according to the present disclosure preferably contains a hydrogen donor compound. In the photosensitive resin composition according to the present disclosure, the hydrogen donor compound has the effect of further improving the sensitivity of the photopolymerization initiator to actinic rays and suppressing the inhibition of polymerization of the polymerizable compound by oxygen. Examples of the hydrogen donor compound include amines, such as the compounds described in M.R. Sander et al., Journal of Polymer Society, Vol. 10, p. 3173 (1972), JP-B-20189 / 1969, JP-A-51-82102, JP-A-52-134692, JP-A-59-138205, JP-A-60-84305, JP-A-62-18537, JP-A-64-33104, and Research Disclosure No. 33825. Specific examples of the hydrogen donor compound include triethanolamine, p-dimethylaminobenzoic acid ethyl ester, p-formyldimethylaniline, and p-methylthiodimethylaniline.

[0109] Further, examples of hydrogen donor compounds include amino acid compounds (N-phenylglycine, etc.), organometallic compounds (tributyltin acetate, etc.) described in JP-B-48-42965, hydrogen donors described in JP-B-55-34414, and sulfur compounds (trithiane, etc.) described in JP-A-6-308727.

[0110] The photosensitive resin composition according to the present disclosure may contain only one type of hydrogen donor compound, or may contain two or more types. When the photosensitive resin composition according to the present disclosure contains a hydrogen donor compound, the content of the hydrogen donor compound is preferably 0.01% by mass to 10% by mass, more preferably 0.03% by mass to 5% by mass, and even more preferably 0.05% by mass to 3% by mass, relative to the total solid content of the photosensitive resin composition, from the viewpoint of improving the curing rate by balancing the polymerization propagation rate and chain transfer, for example.

[0111] <Solvent> The photosensitive resin composition according to the present disclosure preferably contains a solvent. When the photosensitive resin composition according to the present disclosure contains a solvent, it tends to be easier to form a photosensitive layer by coating.

[0112] As the solvent, any commonly used solvent can be used without any particular limitation. The solvent is preferably an organic solvent. Examples of organic solvents include methyl ethyl ketone, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate (also known as 1-methoxy-2-propyl acetate), diethylene glycol ethyl methyl ether, cyclohexanone, methyl isobutyl ketone, ethyl lactate, methyl lactate, caprolactam, n-propanol, and 2-propanol. As the solvent, a mixed solvent of methyl ethyl ketone and propylene glycol monomethyl ether acetate, or a mixed solvent of diethylene glycol ethyl methyl ether and propylene glycol monomethyl ether acetate is preferred.

[0113] As the solvent, the solvents described in paragraphs 0054 and 0055 of US Patent Application Publication No. 2005 / 282073 can also be used, the contents of which are incorporated herein by reference. Furthermore, as the solvent, an organic solvent having a boiling point of 180° C. to 250° C. (high boiling point solvent) can also be used, if necessary.

[0114] When the photosensitive resin composition according to the present disclosure contains a solvent, it may contain only one type of solvent, or may contain two or more types of solvent. When the photosensitive resin composition according to the present disclosure contains a solvent, the solid content of the photosensitive resin composition according to the present disclosure is preferably 5% by mass to 80% by mass, more preferably 5% by mass to 40% by mass, and particularly preferably 5% by mass to 30% by mass, relative to the total mass of the photosensitive resin composition.

[0115] When the photosensitive resin composition according to the present disclosure contains a solvent, the viscosity of the photosensitive resin composition at 25°C is, for example, preferably 1 mPa·s to 50 mPa·s, more preferably 2 mPa·s to 40 mPa·s, and even more preferably 3 mPa·s to 30 mPa·s, from the viewpoint of coatability. The viscosity is measured using a viscometer. For example, a viscometer (product name: VISCOMETER TV-22) manufactured by Toki Sangyo Co., Ltd. can be suitably used as the viscometer. However, the viscometer is not limited to this.

[0116] When the photosensitive resin composition according to the present disclosure contains a solvent, the surface tension of the photosensitive resin composition at 25°C is, for example, preferably 5 mN / m to 100 mN / m, more preferably 10 mN / m to 80 mN / m, and even more preferably 15 mN / m to 40 mN / m, from the viewpoint of coatability. The surface tension is measured using a surface tensiometer. For example, a surface tensiometer (trade name: Automatic Surface Tensiometer CBVP-Z) manufactured by Kyowa Interface Science Co., Ltd. can be suitably used as the surface tensiometer. However, the surface tensiometer is not limited to this.

[0117] <Other ingredients> The photosensitive resin composition according to the present disclosure may contain components other than the components already described (so-called other components). Other components include particles (for example, metal oxide particles), colorants, and the like. Further, examples of other components include the thermal polymerization inhibitors described in paragraph 0018 of Japanese Patent No. 4502784, and other additives described in paragraphs 0058 to 0071 of JP-A No. 2000-310706.

[0118] -particle- The photosensitive resin composition according to the present disclosure may contain particles (for example, metal oxide particles; the same applies hereinafter) for the purpose of adjusting the refractive index, light transmittance, and the like. The metals in the metal oxide particles also include metalloids such as B, Si, Ge, As, Sb, and Te.

[0119] The average primary particle size of the particles is preferably from 1 nm to 200 nm, and more preferably from 3 nm to 80 nm, from the viewpoint of the transparency of the cured film, for example. The average primary particle size of particles is calculated by measuring the particle sizes of 200 random particles using an electron microscope and calculating the arithmetic mean of the measurement results. If the particle shape is not spherical, the particle size is taken to be the longest side.

[0120] When the photosensitive resin composition according to the present disclosure contains particles, it may contain only one type of particles or two or more types of particles differing in metal type, size, etc. The photosensitive resin composition according to the present disclosure preferably does not contain particles, or the particle content is more than 0% by mass and not more than 35% by mass, relative to the total solid content of the photosensitive resin composition; more preferably does not contain particles, or the particle content is more than 0% by mass and not more than 10% by mass, relative to the total solid content of the photosensitive resin composition; even more preferably does not contain particles, or the particle content is more than 0% by mass and not more than 5% by mass, relative to the total solid content of the photosensitive resin composition; even more preferably does not contain particles, or the particle content is more than 0% by mass and not more than 1% by mass, relative to the total solid content of the photosensitive resin composition; and particularly preferably does not contain particles.

[0121] -Coloring agent- The photosensitive resin composition according to the present disclosure may contain a small amount of a colorant (pigment, dye, etc.), but preferably does not substantially contain a colorant, for example, from the viewpoint of transparency. When the photosensitive resin composition according to the present disclosure contains a colorant, the content of the colorant is preferably less than 1 mass %, more preferably less than 0.1 mass %, based on the total solid content of the photosensitive resin composition.

[0122] <Application> The use of the photosensitive resin composition according to the present disclosure is not particularly limited, but since the resulting cured film has low moisture permeability and excellent bending resistance, it can be suitably used as a photosensitive resin composition for touch panels, more suitably used as a photosensitive resin composition for forming a protective film in a touch panel, and particularly suitably used as a photosensitive resin composition for forming an electrode protective film in a touch panel.

[0123] (cured film) The cured film according to the present disclosure is a film obtained by curing the photosensitive resin composition according to the present disclosure. When the photosensitive resin composition according to the present disclosure contains a solvent, the cured film according to the present disclosure is a cured film obtained by curing the solid content of the photosensitive resin composition according to the present disclosure. Furthermore, when the photosensitive resin composition according to the present disclosure contains a solvent, it is preferable to apply the photosensitive resin composition according to the present disclosure to a substrate in the form of a film, then remove at least a portion of the solvent by a known method such as heat drying, air drying, or reduced pressure drying, and then perform curing to form a cured film. The cured film may have a desired pattern shape. The cured film according to the present disclosure can be suitably used as an interlayer insulating film (a so-called insulating film), an overcoat film (a so-called protective film), etc. Furthermore, since the cured film according to the present disclosure has excellent film physical properties, it can be suitably used in organic electroluminescence display devices, liquid crystal display devices, etc. Furthermore, the cured film according to the present disclosure can be suitably used as a protective film for a touch panel, and can be particularly suitably used as an electrode protective film for a touch panel. The thickness of the cured film according to the present disclosure is not particularly limited, but is preferably from 1 μm to 20 μm, more preferably from 2 μm to 15 μm, and even more preferably from 3 μm to 12 μm.

[0124] (transfer film) The transfer film according to the present disclosure has a temporary support and a photosensitive layer containing at least the solid content of the photosensitive resin composition according to the present disclosure, and preferably has a temporary support and a photosensitive layer made of the photosensitive resin composition according to the present disclosure or obtained by drying the photosensitive resin composition.

[0125] <Temporary support> The transfer film according to the present disclosure has a temporary support. The temporary support is preferably a film, more preferably a resin film, which is flexible and does not significantly deform, shrink, or stretch under pressure or under pressure and heat. Examples of such films include polyethylene terephthalate films (eg, biaxially oriented polyethylene terephthalate films), cellulose triacetate films, polystyrene films, polyimide films, and polycarbonate films. Among these, a biaxially stretched polyethylene terephthalate film is particularly preferred as the temporary support. Furthermore, it is preferable that the film used as the temporary support is free from deformations such as wrinkles and scratches. The temporary support preferably has high transparency from the viewpoint of enabling pattern exposure through the temporary support, and the transmittance at 365 nm is preferably 60% or more, more preferably 70% or more. From the viewpoints of pattern formability during pattern exposure through the temporary support and transparency of the temporary support, it is preferable that the haze of the temporary support is small. Specifically, the haze value of the temporary support is preferably 2% or less, more preferably 0.5% or less, and particularly preferably 0.1% or less. From the viewpoint of pattern formation during pattern exposure through the temporary support and the transparency of the temporary support, it is preferable that the number of fine particles, foreign matter, and defects contained in the temporary support is small. The number of fine particles, foreign matter, and defects with a diameter of 1 μm or more is 50 / 10 mm. 2 Preferably, it is 10 pieces / 10 mm or less. 2 It is more preferable that the number of pieces is 3 pieces / 10 mm or less. 2 More preferably, it is 0 pieces / 10 mm or less. 2 It is particularly preferred that: Furthermore, a layer containing fine particles (lubricant layer) may be provided on the surface of the temporary support to further improve handling. The lubricant layer may be provided on one side or both sides of the temporary support. The diameter of the particles contained in the lubricant layer may be 0.05 μm to 0.8 μm. The thickness of the lubricant layer may be 0.05 μm to 1.0 μm.

[0126] The thickness of the temporary support is not particularly limited, but is preferably 5 μm to 200 μm, and from the viewpoint of ease of handling and versatility, is more preferably 10 μm to 150 μm, and even more preferably 10 to 50 μm. Examples of the temporary support include a biaxially oriented polyethylene terephthalate film having a thickness of 16 μm, a biaxially oriented polyethylene terephthalate film having a thickness of 12 μm, and a biaxially oriented polyethylene terephthalate film having a thickness of 9 μm. Preferred embodiments of the temporary support are described, for example, in paragraphs 0017 to 0018 of JP 2014-85643 A, paragraphs 0019 to 0026 of JP 2016-27363 A, paragraphs 0041 to 0057 of WO 2012 / 081680 A, and paragraphs 0029 to 0040 of WO 2018 / 179370 A, the contents of which are incorporated herein by reference. The temporary support may also be available as, for example, Lumirror (registered trademark) 16FB40 manufactured by Toray Industries, Inc., or Lumirror (registered trademark) 16QS62 (16KS40), Cosmoshine (registered trademark) A4100, Cosmoshine (registered trademark) A4300, or Cosmoshine (registered trademark) A8300 manufactured by Toyobo Co., Ltd. Particularly preferred embodiments of the temporary support include a 16 μm thick biaxially oriented polyethylene terephthalate film, a 12 μm thick biaxially oriented polyethylene terephthalate film, and a 10 μm thick biaxially oriented polyethylene terephthalate film.

[0127] <Photosensitive layer> The transfer film according to the present disclosure has a photosensitive layer containing at least the solid content of the photosensitive resin composition according to the present disclosure, and preferably has a photosensitive layer made of the photosensitive resin composition according to the present disclosure or obtained by drying the photosensitive resin composition. When the photosensitive resin composition according to the present disclosure contains a solvent, it is preferable to remove at least a portion of the solvent by a known method before forming the photosensitive layer. The solvent does not need to be completely removed. For example, the content of the solvent in the photosensitive layer is preferably 5% by mass or less, more preferably 1% by mass or less, and particularly preferably 0.5% by mass or less, based on the total mass of the photosensitive layer.

[0128] The thickness of the photosensitive layer is not particularly limited, but is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 12 μm or less. A photosensitive layer having a thickness of 20 μm or less is advantageous in terms of reducing the overall thickness of the transfer film, improving the transmittance of the photosensitive layer or the resulting cured film, and suppressing yellowing of the photosensitive layer or the resulting cured film. From the viewpoint of manufacturability, the thickness of the photosensitive layer is, for example, preferably 1 μm or more, more preferably 2 μm or more, and particularly preferably 3 μm or more. The thickness of the photosensitive layer is calculated as the average value of measurements taken at any five points by cross-sectional observation using a scanning electron microscope (SEM).

[0129] The refractive index of the photosensitive layer is not particularly limited, but is preferably from 1.47 to 1.56, more preferably from 1.50 to 1.53, even more preferably from 1.50 to 1.52, and particularly preferably from 1.51 to 1.52.

[0130] The method for forming the photosensitive layer is not particularly limited, and any known method can be used. An example of a method for forming the photosensitive layer is a method in which a photosensitive resin composition containing a solvent is applied onto a temporary support, and then dried as necessary to form the photosensitive layer. As the coating method, a known method can be used. Examples of the coating method include printing, spraying, roll coating, bar coating, curtain coating, spin coating, and die coating (that is, slit coating). Among these, the die coating method is preferred as the coating method. As the drying method, known methods such as natural drying, heat drying, and reduced pressure drying can be used, and these methods can be applied alone or in combination. In this disclosure, "drying" means removing at least a portion of the solvent contained in the composition.

[0131] <Second Resin Layer> The transfer film according to the present disclosure may further include a second resin layer on the side opposite to the side on which the temporary support is present, as viewed from the photosensitive layer. The second resin layer is preferably a refractive index adjusting layer. The second resin layer may also contain a compound A. The preferred embodiment and preferred content of the compound A are the same as those in the photosensitive layer.

[0132] The second resin layer is preferably disposed adjacent to the photosensitive layer. From the viewpoint of suppressing visibility of the wiring, the refractive index of the second resin layer is preferably higher than the refractive index of the photosensitive layer. The refractive index of the second resin layer is preferably 1.50 or more, more preferably 1.55 or more, even more preferably 1.60 or more, and particularly preferably 1.70 or more. The upper limit of the refractive index of the second resin layer is not particularly limited, but is preferably 2.10 or less, more preferably 1.85 or less, even more preferably 1.78 or less, and particularly preferably 1.74 or less.

[0133] The second resin layer may be photocurable (i.e., photosensitive), may be thermosetting, or may have both photocurable and thermosetting properties. However, from the viewpoint of forming a cured film with excellent strength, it is preferable that the second resin layer be photocurable. The second resin layer preferably has alkali solubility (for example, solubility in a weak alkaline aqueous solution).

[0134] The thickness of the second resin layer is not particularly limited. The thickness of the second resin layer is preferably 50 nm or more and 500 nm or less, more preferably 55 nm or more and 110 nm or less, and even more preferably 60 nm or more and 100 nm or less. The thickness of the second resin layer is calculated as the average value of measurements taken at any five points by cross-sectional observation using a scanning electron microscope (SEM).

[0135] The method for controlling the refractive index of the second resin layer is not particularly limited, and examples thereof include a method of using a resin having a predetermined refractive index alone, a method of using a resin and metal oxide particles or metal particles, and a method of using a complex of a metal salt and a resin. The type of metal oxide particles is not particularly limited, and known metal oxide particles can be used. The metals in the metal oxide particles also include metalloids such as B, Si, Ge, As, Sb, and Te. From the viewpoint of transparency, the average primary particle size of the particles is preferably 1 nm to 200 nm, and more preferably 3 nm to 80 nm. The average primary particle size of particles is calculated by measuring the particle sizes of 200 random particles using an electron microscope and calculating the arithmetic mean of the measurement results. If the particle shape is not spherical, the particle size is taken to be the longest side. Specifically, the metal oxide particles are preferably at least one selected from the group consisting of zirconium oxide particles (ZrO2 particles), Nb2O5 particles, titanium oxide particles (TiO2 particles), and silicon dioxide particles (SiO2 particles), and composite particles thereof. Among these, at least one type of metal oxide particles selected from the group consisting of zirconium oxide particles and titanium oxide particles is more preferred, from the viewpoint of making it easier to adjust the refractive index of the second resin layer to 1.6 or more, for example. Commercially available metal oxide particles include calcined zirconium oxide particles (manufactured by CIK Nanotech Co., Ltd., product name: ZRPGM15WT%-F04), calcined zirconium oxide particles (manufactured by CIK Nanotech Co., Ltd., product name: ZRPGM15WT%-F74), calcined zirconium oxide particles (manufactured by CIK Nanotech Co., Ltd., product name: ZRPGM15WT%-F75), calcined zirconium oxide particles (manufactured by CIK Nanotech Co., Ltd., product name: ZRPGM15WT%-F76), zirconium oxide particles (Nanouse OZ-S30M, manufactured by Nissan Chemical Industries, Ltd.), and zirconium oxide particles (Nanouse OZ-S30K, manufactured by Nissan Chemical Industries, Ltd.).

[0136] When the second resin layer contains metal oxide particles, the second resin layer may contain only one type of metal oxide particles, or may contain two or more types of metal oxide particles.

[0137] The content of the metal oxide particles is preferably 1% by mass to 95% by mass, more preferably 20% by mass to 90% by mass, and even more preferably 40% by mass to 85% by mass, relative to the total mass of the second resin layer, from the viewpoint of improving the concealment of the object to be concealed, such as an electrode pattern, and effectively improving the visibility of the object to be concealed. When titanium oxide is used as the metal oxide particles, the content of the titanium oxide particles is preferably 1% by mass to 95% by mass, more preferably 20% by mass to 90% by mass, and even more preferably 40% by mass to 85% by mass, relative to the total mass of the second resin layer.

[0138] The second resin layer preferably contains a binder polymer and an ethylenically unsaturated compound. For the components of the second resin layer, reference can be made to the components of the curable second resin layer described in paragraphs 0019 to 0040 and 0144 to 0150 of JP 2014-108541 A, the components of the transparent layer described in paragraphs 0024 to 0035 and 0110 to 0112 of JP 2014-10814 A, and the components of the composition having an ammonium salt described in paragraphs 0034 to 0056 of WO 2016 / 009980 A. The binder polymer contained in the second resin layer may be the same as the binder polymer contained in the photosensitive layer, and the preferred range is also the same. As the ethylenically unsaturated compound contained in the second resin layer, the same compounds as the radical polymerizable compound having an ethylenically unsaturated group contained in the photosensitive layer can be used, and the preferred ranges are also the same.

[0139] The second resin layer may also contain a metal oxidation inhibitor other than compound A from the viewpoint of inhibiting oxidation of the metal in contact with the second resin layer. Preferred examples of metal oxidation inhibitors other than Compound A include compounds having an aromatic ring containing a nitrogen atom in the molecule. Examples of metal oxidation inhibitors other than Compound A include imidazole, triazole, benzimidazole, tetrazole, mercaptothiadiazole, benzotriazole, and purine. In addition, the second resin layer preferably contains adenine as the compound A from the viewpoint of inhibiting oxidation of the metal in contact with the second resin layer.

[0140] From the viewpoint of manufacturing suitability, the second resin layer may contain an amine compound having a chain group with three or more atoms. Examples of the amine compound having a chain group with three or more atoms include (3-(diethylamino)-1,2-propanediol and N-methyldiethanolamine.

[0141] The second resin layer may contain components other than the above-mentioned components. Other components that can be contained in the second resin layer include the same components as those contained in the photosensitive layer described above. The second resin layer preferably contains a surfactant as another component.

[0142] The method for forming the second resin layer is not particularly limited. An example of a method for forming the second resin layer is a method in which a composition for forming a second resin layer containing an aqueous solvent is applied to the photosensitive layer already formed on a temporary support, and the composition is dried as necessary to form the second resin layer. Specific examples of the coating and drying methods in the method for forming the second resin layer are the same as those in the method for forming the photosensitive layer.

[0143] <Protective film> The transfer film according to the present disclosure may further have a protective film on the side of the photosensitive layer opposite to the temporary support. When the transfer film according to the present disclosure has a second resin layer on the side opposite the temporary support from the photosensitive layer, it is preferable that the protective film be on the side opposite the temporary support from the second resin layer. The protective film is preferably the outermost layer on the surface of the transfer film according to the present disclosure opposite to the temporary support. Examples of the protective film include a polyethylene terephthalate film, a polypropylene film, a polyethylene film, a polystyrene film, and a polycarbonate film. As the protective film, for example, the films described in paragraphs 0083 to 0087 and 0093 of JP-A No. 2006-259138 may be used. The protective film is also available as, for example, Alphan (registered trademark) FG-201 manufactured by Oji F-Tex Co., Ltd., Alphan (registered trademark) E-201F manufactured by Oji F-Tex Co., Ltd., Therapeel (registered trademark) 25WZ manufactured by Toray Advanced Film Co., Ltd., or Lumirror (registered trademark) 16QS62 (16KS40) manufactured by Toray Industries, Inc. In addition, the number of fisheyes with a diameter of 80 μm or more contained in the protective film is 5 / m 2 The following is preferable: "Fisheyes" are foreign matter, undissolved matter, oxidized and deteriorated matter, etc., that are trapped in the film when the material is thermally melted and then kneaded, extruded, biaxially stretched, cast, or other methods are used to produce the film.

[0144] The number of particles with a diameter of 3 μm or more contained in the protective film is 30 / mm 2 It is preferable that the number of particles is less than 10 / mm 2 It is more preferable that the number of particles is 5 or less per mm. 2 It is more preferable that the following is satisfied: This makes it possible to suppress defects caused by unevenness due to particles contained in the protective film being transferred to the photosensitive resin layer.

[0145] From the viewpoint of providing windability, the protective film has an arithmetic mean roughness Ra of the surface opposite to the surface in contact with the photosensitive layer of preferably 0.01 μm or more, more preferably 0.02 μm or more, and even more preferably 0.03 μm or more, while from the viewpoint of suppressing defects during transfer, Ra is preferably less than 0.50 μm, more preferably 0.40 μm or less, and even more preferably 0.30 μm or less. From the viewpoint of suppressing defects during transfer, the surface roughness Ra of the protective film on the surface in contact with the photosensitive layer is preferably 0.01 μm or more, more preferably 0.02 μm or more, and even more preferably 0.03 μm or more, and is preferably less than 0.50 μm, more preferably 0.40 μm or less, and even more preferably 0.30 μm or less.

[0146] <Thermoplastic resin layer> The transfer film according to the present disclosure may further include a thermoplastic resin layer between the temporary support and the photosensitive layer. When the transfer film further includes a thermoplastic resin layer, bubbles caused by lamination are less likely to occur when the transfer film is transferred to a substrate to form a laminate. When this laminate is used in an image display device, image unevenness and the like are less likely to occur, and excellent display characteristics can be obtained. The thermoplastic resin layer is preferably alkali-soluble. The thermoplastic resin layer functions as a cushioning material that absorbs unevenness on the substrate surface during transfer. The unevenness on the substrate surface includes images, electrodes, wiring, etc. that have already been formed. The thermoplastic resin layer preferably has a property of being deformable in accordance with the unevenness.

[0147] The thermoplastic resin layer preferably contains an organic polymer substance described in JP-A-5-72724, and more preferably contains an organic polymer substance having a softening point of about 80°C or less according to the Vicat method (specifically, a polymer softening point measurement method according to American Standard Testing Methods ASTM D1235).

[0148] The thickness of the thermoplastic resin layer is, for example, preferably 3 μm to 30 μm, more preferably 4 μm to 25 μm, and even more preferably 5 μm to 20 μm. When the thickness of the thermoplastic resin layer is 3 μm or more, the ability to conform to the irregularities on the substrate surface is improved, and the irregularities on the substrate surface can be absorbed more effectively. When the thickness of the thermoplastic resin layer is 30 μm or less, the manufacturing suitability is further improved, and for example, the burden of drying (i.e., drying to remove the solvent) when coating and forming the thermoplastic resin layer on the temporary support is further reduced, and the development time of the thermoplastic resin layer after transfer is further shortened. The thickness of the thermoplastic resin layer is calculated as the average value of measurements taken at any five points by cross-sectional observation using a scanning electron microscope (SEM).

[0149] The thermoplastic resin layer can be formed by applying a thermoplastic resin layer-forming composition containing a solvent and a thermoplastic organic polymer to a temporary support, and drying it as necessary. Specific examples of the coating and drying methods in the method for forming the thermoplastic resin layer are the same as those in the method for forming the photosensitive layer. The solvent is not particularly limited as long as it dissolves the polymer component that forms the thermoplastic resin layer. The solvent may be an organic solvent (eg, methyl ethyl ketone, cyclohexanone, propylene glycol monomethyl ether acetate, n-propanol, and 2-propanol).

[0150] The thermoplastic resin layer preferably has a viscosity of 1,000 Pa·s to 10,000 Pa·s measured at 100°C. Furthermore, the viscosity of the thermoplastic resin layer measured at 100°C is preferably lower than the viscosity of the photosensitive layer measured at 100°C.

[0151] <Middle class> The transfer film according to the present disclosure may further have an intermediate layer between the temporary support and the photosensitive layer. When the transfer film according to the present disclosure has a thermoplastic resin layer, the intermediate layer is preferably disposed between the thermoplastic resin layer and the photosensitive layer. The intermediate layer may contain, for example, at least one polymer selected from the group consisting of polyvinyl alcohol, polyvinylpyrrolidone, and cellulose. Furthermore, as the intermediate layer, the one described as a "separation layer" in Japanese Patent Application Laid-Open No. 5-72724 can also be used.

[0152] When producing a transfer film having a thermoplastic resin layer, an intermediate layer, and a photosensitive layer in this order on a temporary support, the intermediate layer can be formed, for example, by applying a composition for forming an intermediate layer containing a solvent that does not dissolve the thermoplastic resin layer and the above-mentioned polymer as a component of the intermediate layer, and drying it as necessary. In detail, first, a thermoplastic resin layer-forming composition is applied onto a temporary support and dried as necessary to form a thermoplastic resin layer. Next, an intermediate layer-forming composition is applied onto the formed thermoplastic resin layer and dried as necessary to form an intermediate layer. Next, a photosensitive resin composition containing an organic solvent (so-called photosensitive layer-forming composition) is applied onto the formed intermediate layer and dried to form a photosensitive layer. Note that the organic solvent contained in the photosensitive layer-forming composition is preferably an organic solvent that does not dissolve the intermediate layer. Specific examples of the coating and drying methods in the method for forming the intermediate layer are the same as those in the method for forming the photosensitive layer.

[0153] -impurities- In the transfer film according to the present disclosure, it is preferable that the photosensitive layer and the second resin layer have a low impurity content in order to improve reliability and patterning properties. Specific examples of impurities include sodium, potassium, magnesium, calcium, iron, manganese, copper, aluminum, titanium, chromium, cobalt, nickel, zinc, tin, and ions thereof, as well as halide ions (chloride ions, bromide ions, iodide ions, etc.). Among these, sodium ions, potassium ions, and chloride ions are easily mixed in as impurities, so it is particularly preferable to set the contents to the following: The impurity content in each layer is preferably 1,000 ppm or less by mass, more preferably 200 ppm or less, even more preferably 40 ppm or less, particularly preferably 10 ppm or less, and most preferably 5 ppm or less. Although the lower limit is not particularly set, from the viewpoint of the limit that can be practically reduced and the measurement limit, it can be 10 ppb or more, and can be 100 ppb or more by mass. Methods for reducing the amount of impurities to the above range include selecting impurity-free raw materials for each layer, preventing impurities from being mixed in during layer formation, removing them by washing, etc. By using such methods, the amount of impurities can be kept within the above range. The amount of impurities can be determined by known methods such as ICP (Inductively Coupled Plasma) emission spectroscopy, atomic absorption spectroscopy, and ion chromatography.

[0154] Furthermore, it is preferable that the content of compounds such as benzene, formaldehyde, trichloroethylene, 1,3-butadiene, carbon tetrachloride, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, and hexane in each layer is low. The content of these compounds in each layer is preferably 1,000 ppm or less by mass, more preferably 200 ppm or less, even more preferably 40 ppm or less, particularly preferably 10 ppm or less, and most preferably 5 ppm or less. There is no particular lower limit, but from the viewpoint of the limit that can be practically reduced and the measurement limit, it can be 10 ppb or more, and can be 100 ppb or more by mass. The content of the compound impurities can be reduced in the same manner as for the metal impurities described above, and can be quantified by known measurement methods.

[0155] -moisture- In the transfer film according to the present disclosure, from the viewpoint of improving lamination properties, reliability, and patterning properties, the moisture content of the photosensitive layer and the second resin layer is preferably 0.01% by mass or more and 1.0% by mass or less, and more preferably 0.1% by mass or more and 0.5% by mass or less, relative to the total mass of the photosensitive layer or the second resin layer. The photosensitive layer and the second resin layer are preferably achromatic. Specifically, the total reflection (incident angle 8°, light source: D-65 (2° visual field)) is preferably achromatic in the CIE1976 (L*, a*, b*) color space. * The value is preferably 10 to 90, and a * The value is preferably -1.0 to 1.0, and b * The value is preferably between -1.0 and 1.0.

[0156] -Examples of transfer film- Fig. 1 is a schematic cross-sectional view of a specific example of a transfer film according to the present disclosure, a transfer film 10. As shown in Fig. 1, the transfer film 10 has a laminated structure of a protective film 16 / a second resin layer 20A / a photosensitive layer 18A / a temporary support 12 (i.e., a laminated structure in which the temporary support 12, the photosensitive layer 18A, the second resin layer 20A, and the protective film 16 are arranged in this order). However, the transfer film according to the present disclosure is not limited to the transfer film 10, and for example, the second resin layer 20A and the protective film 16 may be omitted. In addition, at least one of the thermoplastic resin layer and the intermediate layer described above may be present between the temporary support 12 and the photosensitive layer 18A.

[0157] The second resin layer 20A is a layer disposed on the opposite side of the photosensitive layer 18A from the side where the temporary support 12 is present, and has a refractive index of 1.50 or more at a wavelength of 550 nm. The transfer film 10 is a negative material (so-called negative film).

[0158] The method for producing the transfer film 10 is not particularly limited. A method for manufacturing the transfer film 10 includes, for example, a step of forming a photosensitive layer 18A on a temporary support 12, a step of forming a second resin layer 20A on the photosensitive layer 18A, and a step of forming a protective film 16 on the second resin layer 20A, in this order. The method for manufacturing the transfer film 10 may include a step of volatilizing ammonia, as described in paragraph 0056 of International Publication No. 2016 / 009980, between the step of forming the second resin layer 20A and the step of forming the protective film 16. After being produced, the transfer film according to the present disclosure is preferably stored in a refrigerated state in a rolled state until it is used. The refrigeration temperature can be, for example, 2°C or higher and 10°C or lower.

[0159] (Laminate and Capacitive Input Device) The laminate according to the present disclosure includes a substrate and a cured film obtained by curing the photosensitive resin composition according to the present disclosure. The laminate according to the present disclosure may include the cured film according to the present disclosure, but may also include a substrate, an electrode, and and the cured film according to the present disclosure are preferably laminated in this order. The cured film may be in the shape of a desired pattern. The capacitive input device according to the present disclosure includes the cured film according to the present disclosure or the laminate according to the present disclosure. The substrate is preferably a substrate that includes electrodes of a capacitive input device. The electrodes are preferably electrodes of a capacitive input device.

[0160] The electrodes of the capacitance type input device may be transparent electrode patterns or may be routed wiring. In the laminate, the electrodes of the capacitance type input device are preferably electrode patterns, more preferably transparent electrode patterns. The laminate according to the present disclosure and the cured film obtained by curing the photosensitive resin composition according to the present disclosure are preferably achromatic. Specifically, the total reflection (incident angle 8°, light source: D-65 (2° field of view)) is preferably achromatic in the L*, a*, b* color space of the pattern. * The value is preferably 10 to 90, and the pattern a * The value is preferably -1.0 to 1.0, and the b * The value is preferably between -1.0 and 1.0.

[0161] The laminate according to the present disclosure preferably has a substrate, a transparent electrode pattern, a second resin layer arranged adjacent to the transparent electrode pattern, and a photosensitive layer arranged adjacent to the second resin layer, and the refractive index of the second resin layer is higher than the refractive index of the photosensitive layer. The refractive index of the second resin layer is preferably 1.6 or more. When the laminate has the above-mentioned structure, the ability to conceal the transparent electrode pattern is improved.

[0162] The substrate is preferably a glass substrate or a resin substrate. The substrate is preferably a transparent substrate, and more preferably a transparent resin substrate.

[0163] The refractive index of the substrate is preferably 1.50 to 1.52. The glass substrate may be made of tempered glass such as Corning Gorilla Glass (registered trademark). As the resin substrate, it is preferable to use at least one of those that are optically free of distortion and those that are highly transparent, and examples include substrates made of resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), triacetyl cellulose (TAC), polyimide (PI), polybenzoxazole (PBO), and cycloolefin polymer (COP). As the material for the transparent substrate, the materials described in JP-A Nos. 2010-86684, 2010-152809, and 2010-257492 are preferred.

[0164] A suitable example of the capacitance type input device is a touch panel. The touch panel electrode may be, for example, a transparent electrode pattern disposed in at least the image display area of ​​the touch panel, and may extend from the image display area to the frame of the touch panel. An example of the touch panel wiring is a lead wiring (so-called extraction wiring) that is arranged on the frame of the touch panel. A preferred embodiment of the touch panel substrate and touch panel is one in which a portion of the lead-out wiring is laminated on the portion of the transparent electrode pattern that extends to the frame portion of the touch panel, thereby electrically connecting the transparent electrode pattern and the lead-out wiring.

[0165] The material of the transparent electrode pattern is preferably a metal oxide film such as ITO (indium tin oxide) or IZO (indium zinc oxide), or a metal mesh or a thin metal wire such as silver nanowire. Examples of the thin metal wires include thin wires of silver, copper, etc. Among them, conductive silver materials such as silver mesh and silver nanowires are preferred.

[0166] The material of the lead wiring is preferably metal. Examples of metals that can be used for the wiring include gold, silver, copper, molybdenum, aluminum, titanium, chromium, zinc, and manganese, as well as alloys of two or more of these metal elements. Copper, molybdenum, aluminum, and titanium are preferred as the material for the wiring, with copper being particularly preferred.

[0167] The electrode protective film for a touch panel formed using the transfer film according to the present disclosure is provided to cover the electrodes, etc. (i.e., at least one of the electrodes for a touch panel and the wiring for a touch panel) directly or via another layer, for the purpose of protecting the electrodes, etc. The preferred range of the thickness of the touch panel electrode protective film is the same as the preferred range of the thickness of the photosensitive layer described above.

[0168] The electrode protective film (preferably, the electrode protective film for a touch panel) may have an opening. The openings can be formed by dissolving the unexposed areas of the photosensitive layer with a developer.

[0169] The touch panel may further include a first refractive index-adjusting layer between the electrodes and the touch panel electrode protection layer (for example, see a first specific example of a touch panel described later). The preferred embodiment of the first refractive index adjusting layer is the same as the preferred embodiment of the second resin layer that the transfer film may have, except that, if the second resin layer is curable, the first refractive index adjusting layer is a cured layer, and it goes without saying that the preferred embodiments of the second resin layer, such as photocurability, thermosetting, and alkali-solubility, do not apply to the preferred embodiment of the first refractive index adjusting layer. The first refractive index adjusting layer may be formed by applying and drying a composition for forming the first refractive index adjusting layer, or may be formed by transferring a refractive index adjusting layer from a transfer film having a refractive index adjusting layer separately. The touch panel having the first refractive index adjusting layer is preferably formed by using a transfer film according to an embodiment of the present disclosure having a second resin layer and transferring a photosensitive layer and the second resin layer from the transfer film. In this case, the photosensitive layer in the transfer film forms a touch panel electrode protective layer, and the second resin layer in the transfer film forms the first refractive index adjusting layer.

[0170] The touch panel or the substrate for a touch panel may also have a second refractive index-adjusting layer between the substrate and the electrodes or the like (for example, see the first specific example of the touch panel described later). A preferred embodiment of the second refractive index adjusting layer is the same as a preferred embodiment of the second resin layer that the transfer film may have.

[0171] An embodiment in which the touch panel has a first refractive index adjustment layer (more preferably, an embodiment in which the touch panel has a first refractive index adjustment layer and a second refractive index adjustment layer) has the advantage that electrodes and the like are less visible (so-called bone visibility is suppressed).

[0172] For the structure of the touch panel, reference may be made to the structures of the capacitance type input devices described in Japanese Patent Application Laid-Open Nos. 2014-10814 and 2014-108541.

[0173] -First example of a touch panel- 2 is a schematic cross-sectional view of a touch panel 30, which is a first specific example of a touch panel according to the present disclosure. More specifically, FIG. 2 is a schematic cross-sectional view of an image display area of ​​the touch panel 30. As shown in FIG. 2, the touch panel 30 has a structure in which a substrate 32, a second refractive index matching layer 36, a transparent electrode pattern 34 as an electrode for the touch panel, a first refractive index matching layer 20, and a touch panel electrode protection film 18 are arranged in this order. In the touch panel 30, the touch panel electrode protective film 18 and the first refractive index matching layer 20 cover the entire transparent electrode pattern 34. However, the touch panel according to the present disclosure is not limited to this embodiment. The touch panel electrode protective film 18 and the first refractive index matching layer 20 only need to cover at least a portion of the transparent electrode pattern 34.

[0174] The second refractive index matching layer 36 and the first refractive index matching layer 20 preferably cover, directly or continuously via another layer, the first region 40 where the transparent electrode pattern 34 is present and the second region 42 where the transparent electrode pattern 34 is not present, respectively. According to this embodiment, the transparent electrode pattern 34 becomes less visible. The second refractive index-matching layer 36 and the first refractive index-matching layer 20 preferably cover both the first region 40 and the second region 42 directly rather than covering them via another layer. Examples of "other layers" include insulating layers, electrode patterns other than the transparent electrode pattern 34, and the like.

[0175] The first refractive index matching layer 20 is laminated across both the first region 40 and the second region 42. The first refractive index matching layer 20 is adjacent to the second refractive index matching layer 36, and further adjacent to the transparent electrode pattern 34. When the shape of the end of the transparent electrode pattern 34 at the point where it contacts the second refractive index matching layer 36 is tapered as shown in Figure 2, it is preferable that the first refractive index matching layer 20 is laminated along the tapered shape (i.e., at the same inclination as the taper angle).

[0176] The transparent electrode pattern 34 is preferably an ITO transparent electrode pattern. The transparent electrode pattern 34 can be formed, for example, by the following method. An electrode thin film (e.g., an ITO film) is formed by sputtering on the substrate 32 on which the second refractive index matching layer 36 has been formed. Next, an etching protection layer is formed on the formed electrode thin film by applying a photosensitive etching resist or by transferring a photosensitive etching film. Next, the formed etching protection layer is patterned into a desired pattern shape by exposure and development. Next, portions of the electrode thin film that are not covered by the patterned etching protection layer are removed by etching, and the electrode thin film is patterned into a desired shape (i.e., a transparent electrode pattern 34). Next, the patterned etching protection layer is removed using a stripping solution.

[0177] The first refractive index matching layer 20 and the touch panel electrode protection film 18 are formed, for example, on a substrate 32 (i.e., a touch panel substrate) on which a second refractive index matching layer 36 and a transparent electrode pattern 34 are sequentially provided, as follows. First, the transfer film 10 shown in FIG. 1 (that is, the transfer film 10 having a laminated structure of the protective film 16 / second resin layer 20A / photosensitive layer 18A / temporary support 12) is prepared. Next, the protective film 16 is removed from the transfer film 10. Next, the transfer film 10 from which the protective film 16 has been removed is laminated onto a substrate 32 (i.e., a touch panel substrate) on which a second refractive index matching layer 36 and a transparent electrode pattern 34 have been sequentially formed. The lamination is performed such that the second resin layer 20A of the transfer film 10 from which the protective film 16 has been removed is in contact with the transparent electrode pattern 34. This lamination results in a laminate having a layered structure of temporary support 12 / photosensitive layer 18A / second resin layer 20A / transparent electrode pattern 34 / second refractive index matching layer 36 / substrate 32. Next, the temporary support 12 is removed from the laminate. Next, the photosensitive layer 18A and the second resin layer 20A are patternwise cured by patternwise exposure of the laminate from which the temporary support 12 has been removed. The patternwise curing of the photosensitive layer 18A and the second resin layer 20A may be carried out separately by separate patternwise exposures, but is preferably carried out simultaneously by a single patternwise exposure. Next, the non-exposed portions (i.e., non-cured portions) of the photosensitive layer 18A and the second resin layer 20A are removed by development to obtain a touch panel electrode protective film 18 (pattern shape not shown) which is a patterned cured product of the photosensitive layer 18A, and a first refractive index matching layer 20 (pattern shape not shown) which is a patterned cured product of the second resin layer 20A. The photosensitive layer 18A and the second resin layer 20A after pattern exposure may be developed separately by separate development processes, but are preferably developed simultaneously by a single development process.

[0178] Preferred embodiments of lamination, pattern exposure, and development will be described later.

[0179] -Second example of a touch panel- FIG. 3 is a schematic cross-sectional view of a touch panel 90, which is a second specific example of a touch panel according to the present disclosure. As shown in FIG. 3, the touch panel 90 has an image display area 74 and an image non-display area 75 (that is, a frame portion). The touch panel 90 also includes touch panel electrodes on both sides of the substrate 32. In detail, the touch panel 90 includes a first transparent electrode pattern 70 on one side of the substrate 32, and a second transparent electrode pattern 72 on the other side. In the touch panel 90, the lead wiring 56 is connected to each of the first transparent electrode pattern 70 and the second transparent electrode pattern 72. The lead wiring 56 is, for example, a copper wiring. In the touch panel 90, an electrode protection film 18 for the touch panel is formed on one side of the substrate 32 so as to cover the first transparent electrode pattern 70 and the routing wiring 56, and an electrode protection film 18 for the touch panel is formed on the other side of the substrate 32 so as to cover the second transparent electrode pattern 72 and the routing wiring 56. The first refractive index matching layer and the second refractive index matching layer in the first specific example may be formed on one surface and the other surface of the substrate 32, respectively.

[0180] (Touch panel manufacturing method) The method for manufacturing a touch panel according to the present disclosure is not particularly limited, but the following method is preferred. A method for manufacturing a touch panel according to the present disclosure includes: Preparing a touch panel substrate having a structure in which electrodes and the like (i.e., at least one of touch panel electrodes and touch panel wiring) are arranged on a substrate (hereinafter also referred to as the "preparation step"); Forming a photosensitive layer containing the photosensitive resin composition according to the present disclosure on the surface of the touch panel substrate on which electrodes and the like are arranged (hereinafter also referred to as the "photosensitive layer forming step"); pattern-exposing the photosensitive layer formed on the touch panel substrate (hereinafter also referred to as "pattern-exposing step"); The pattern-exposed photosensitive layer is developed to obtain an electrode protective film for a touch panel that protects at least a part of an electrode or the like (hereinafter also referred to as a "developing step"); It is preferred that the compound contains:

[0181] According to a preferred method for producing a touch panel according to the present disclosure, a touch panel can be produced that includes a cured film that has excellent adhesion to a substrate and excellent corrosion-suppressing properties for metals.

[0182] Each step in a preferred method for manufacturing a touch panel according to the present disclosure will now be described.

[0183] <Preparation process> The preparation step is a step for convenience, in which a touch panel substrate having a structure in which electrodes and the like (that is, at least one of touch panel electrodes and touch panel wiring) are arranged on a substrate is prepared. The preparation step may be a step of simply preparing a pre-manufactured touch panel substrate, or may be a step of manufacturing a touch panel substrate. The preferred embodiment of the touch panel substrate is as described above.

[0184] <Photosensitive layer formation process> The photosensitive layer forming step is a step of forming a photosensitive layer containing the photosensitive resin composition according to the present disclosure on the surface of the touch panel substrate on which electrodes and the like are arranged.

[0185] Hereinafter, an embodiment of forming a photosensitive layer containing a photosensitive resin composition according to the present disclosure using a transfer film according to the present disclosure in the photosensitive layer forming step will be described. In this aspect, the transfer film according to the present disclosure is laminated onto the surface of the touch panel substrate on which electrodes, etc. are arranged, and the photosensitive layer in the transfer film according to the present disclosure is transferred onto the surface, thereby forming a photosensitive layer on the surface. Lamination (so-called transfer of the photosensitive layer) can be carried out using a known laminator such as a vacuum laminator or an auto-cut laminator.

[0186] As lamination conditions, general conditions can be applied. The lamination temperature is preferably 80°C to 150°C, more preferably 90°C to 150°C, and even more preferably 100°C to 150°C. When a laminator equipped with a rubber roller is used, the lamination temperature refers to the temperature of the rubber roller. The substrate temperature during lamination is not particularly limited. The substrate temperature during lamination is preferably 10°C to 150°C, more preferably 20°C to 150°C, and even more preferably 30°C to 150°C. When a resin substrate is used as the substrate, the substrate temperature during lamination is preferably 10°C to 80°C, more preferably 20°C to 60°C, and even more preferably 30°C to 50°C. The line pressure during lamination is preferably 0.5 N / cm to 20 N / cm, more preferably 1 N / cm to 10 N / cm, and even more preferably 1 N / cm to 5 N / cm. The conveying speed during lamination (lamination speed) is preferably 0.5 m / min to 5 m / min, and more preferably 1.5 m / min to 3 m / min.

[0187] When using a transfer film having a laminated structure of protective film / photosensitive layer / intermediate layer / thermoplastic resin layer / temporary support, first peel the protective film from the transfer film to expose the photosensitive layer, then attach the transfer film to the touch panel substrate so that the exposed photosensitive layer contacts the surface of the touch panel substrate on which electrodes, etc. are arranged, and then heat and pressure are applied. By this operation, the photosensitive layer of the transfer film is transferred onto the surface of the touch panel substrate on which electrodes, etc. are arranged, forming a laminate having a laminated structure of temporary support / thermoplastic resin layer / intermediate layer / photosensitive layer / electrodes, etc. / substrate. In this laminated structure, the "electrodes, etc. / substrate" portion is the touch panel substrate. Thereafter, if necessary, the temporary support is peeled off from the laminate, although the pattern exposure described below can also be carried out while the temporary support is left in place.

[0188] As an example of a method for transferring a photosensitive layer of a transfer film onto a touch panel substrate, pattern-exposing the layer, and developing the layer, reference can be made to the description in paragraphs 0035 to 0051 of JP-A No. 2006-23696.

[0189] <Pattern exposure process> The pattern exposure step is a step of pattern-exposing the photosensitive layer formed on the touch panel substrate. The term "pattern exposure" refers to a mode of exposing in a pattern, that is, an exposure mode in which exposed areas and non-exposed areas exist. In the photosensitive layer on the touch panel substrate, the exposed areas in the pattern exposure are cured, and finally become a cured film. On the other hand, in the photosensitive layer on the touch panel substrate, the unexposed areas in the pattern exposure do not harden and are dissolved and removed by a developer in the subsequent development step. The unexposed areas can form openings in the cured film after the development step. The pattern exposure may be exposure through a mask or digital exposure using a laser or the like.

[0190] The light source for pattern exposure can be appropriately selected and used as long as it can irradiate light in a wavelength range that can cure the photosensitive layer (for example, 365 nm or 405 nm). Examples of light sources include various lasers, light-emitting diodes (LEDs), ultra-high pressure mercury lamps, high pressure mercury lamps, and metal halide lamps. The exposure dose was 5 mJ / cm 2 ~200mJ / cm 2 and preferably 10 mJ / cm 2 ~200mJ / cm 2 It is more preferable that:

[0191] When a photosensitive layer is formed on a substrate using a transfer film, the pattern exposure may be performed after peeling off the temporary support, or the pattern exposure may be performed before peeling off the temporary support, and then the temporary support may be peeled off. In the exposure step, the photosensitive layer may be subjected to a heat treatment (so-called PEB (Post Exposure Bake)) after the pattern exposure and before development.

[0192] <Developing process> The development process is a process for obtaining an electrode protective film for a touch panel that protects at least a portion of an electrode, etc., by developing the pattern-exposed photosensitive layer (i.e., by dissolving the non-exposed areas in the pattern-exposed area in a developer).

[0193] The developer used for development is not particularly limited, and known developers such as those described in JP-A No. 5-72724 can be used. As the developer, an alkaline aqueous solution is preferably used. Examples of alkaline compounds that can be contained in the alkaline aqueous solution include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and choline (2-hydroxyethyltrimethylammonium hydroxide). The pH of the alkaline aqueous solution at 25°C is preferably 8-13, more preferably 9-12, and particularly preferably 10-12. The content of the alkaline compound in the alkaline aqueous solution is preferably 0.1% by mass to 5% by mass, and more preferably 0.1% by mass to 3% by mass, relative to the total mass of the alkaline aqueous solution.

[0194] The developer may contain an organic solvent that is miscible with water. Examples of the organic solvent include methanol, ethanol, 2-propanol, 1-propanol, butanol, diacetone alcohol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-butyl ether, benzyl alcohol, acetone, methyl ethyl ketone, cyclohexanone, ε-caprolactone, γ-butyrolactone, dimethylformamide, dimethylacetamide, hexamethylphosphoramide, ethyl lactate, methyl lactate, ε-caprolactam, and N-methylpyrrolidone. The concentration of the organic solvent is preferably 0.1% by mass to 30% by mass. The developer may contain a known surfactant. The concentration of the surfactant is preferably 0.01% by mass to 10% by mass. The liquid temperature of the developer is preferably 20°C to 40°C.

[0195] Examples of the development method include puddle development, shower development, shower and spin development, and dip development. In the case of shower development, the developer is sprayed in the form of a shower onto the photosensitive layer after pattern exposure, thereby removing the unexposed areas of the photosensitive layer. When a transfer film having a photosensitive layer and at least one of a thermoplastic resin layer and an intermediate layer is used, after transferring these layers onto the substrate and before developing the photosensitive layer, an alkaline liquid in which the photosensitive layer has low solubility may be sprayed in a shower to remove in advance at least one of the thermoplastic resin layer and the intermediate layer (or both, if both are present). After development, it is preferable to remove development residues by spraying a cleaning agent or the like with a shower and rubbing with a brush or the like. The liquid temperature of the developer is preferably 20°C to 40°C.

[0196] The development step may include a step of carrying out the development and a step of heat-treating (hereinafter also referred to as "post-baking") the cured film obtained by the development. When the substrate is a resin substrate, the post-baking temperature is preferably 100°C to 160°C, and more preferably 130°C to 160°C. This post-baking can also adjust the resistance value of the transparent electrode pattern. When the photosensitive layer contains a carboxyl group-containing (meth)acrylic resin, post-baking can convert at least a portion of the carboxyl group-containing (meth)acrylic resin into a carboxylic acid anhydride, which improves developability and the strength of the cured film.

[0197] The development step may include a step of carrying out the development and a step of exposing the cured film obtained by the development (hereinafter also referred to as "post-exposure"). When the development process includes both a post-exposure step and a post-bake step, it is preferable to carry out the post-bake step after the post-exposure step.

[0198] For details of pattern exposure, development, etc., reference can be made to the descriptions in paragraphs 0035 to 0051 of JP-A No. 2006-23696, for example.

[0199] The touch panel manufacturing method according to the present disclosure may include steps other than the steps already described (so-called other steps). Other steps include known steps (for example, a cleaning step) that may be included in a normal photolithography process. [Example]

[0200] The present disclosure will now be described more specifically with reference to examples. The materials, amounts used, ratios, processing details, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present disclosure. Therefore, the scope of the present disclosure is not limited to the specific examples shown below.

[0201] Example 1 <Preparation of photosensitive transfer material (transfer film)> <<Formation of photosensitive layer>> A coating solution for the photosensitive layer having the following formulation 101 was applied onto a 16 μm-thick polyethylene terephthalate film (temporary support, 16QS62 (16KS40) (manufactured by Toray Industries, Inc.)) using a slit nozzle so as to give a thickness of 4.5 μm after drying. The coating was then dried in a hot air convection dryer with a temperature gradient of 75°C to 120°C to remove the solvent, forming a photosensitive layer.

[0202] -Photosensitive layer coating liquid: Formulation 101 (organic solvent-based resin composition (photosensitive resin composition))- Ethylenically unsaturated compounds A-NOD-N (M-1, 1,9-nonanediol diacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.): 8.41 parts A-DCP (M-3, tricyclodecane dimethanol diacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.): 16.83 parts Aronix TO-2349 (M-4, a polyfunctional ethylenically unsaturated compound having a carboxylic acid group, manufactured by Toagosei Co., Ltd.): 2.80 parts Binder polymer P-1 (the resin shown below, styrene-derived structural unit (St) / dicyclopentanyl methacrylate-derived structural unit (DCPMA) / methacrylic acid-derived structural unit (MAA) / structural unit obtained by adding glycidyl methacrylate to a methacrylic acid-derived structural unit (GMA-MAA) = 41.0 / 15.2 / 23.9 / 19.9 (mol%), Mw = 17,000): 56.32 parts (solid content) Photopolymerization initiator 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyloxime) (D-1, Irgacure OXE-02, manufactured by BASF): 0.32 parts 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (D-2, Irgacure 907, manufactured by BASF): 0.64 parts ·Thermal crosslinkable compound Duranate WT32-B75P (E-3, blocked isocyanate compound, manufactured by Asahi Kasei Chemicals Corporation): 12.50 parts ·Compound A Pyridine-2-carboxylic acid: 0.69 parts Other additives Hydrogen donor compound (AD-1, N-phenylglycine, manufactured by Junsei Chemical Co., Ltd.): 0.10 parts Styrene / maleic anhydride copolymer (4:1 molar ratio) (AD-2, SMA EF-40, acid anhydride content 1.94 mmol / g, weight average molecular weight 10,500, manufactured by Cray Valley): 1.20 parts Surfactant (AD-3, fluorine-based surfactant, Megafac F551A, manufactured by DIC Corporation): 0.32 parts Organic solvent: A 1:1 (mass ratio) mixed solvent of 1-methoxy-2-propyl acetate and methyl ethyl ketone was added so that the solids concentration of the coating liquid for forming the photosensitive layer was 29 mass %.

[0203] [ka]

[0204] <<Formation of second resin layer>> Next, a coating solution for a second resin layer having the following formulation 201 was applied onto the photosensitive layer using a slit nozzle so as to give a dried thickness of 70 nm, and the coating was dried in a hot air convection dryer with a temperature gradient of 40°C to 95°C to remove the solvent, forming a second resin layer disposed in direct contact with the photosensitive layer. The refractive index of the second resin layer was 1.68 at a wavelength of 550 nm at 25°C. Here, formulation 201 was prepared using a resin having an acid group and an aqueous ammonia solution, and the resin having an acid group was neutralized with the aqueous ammonia solution to prepare a coating liquid for a second resin layer, which was an aqueous resin composition containing an ammonium salt of the resin having an acid group.

[0205] - Coating liquid for second resin layer: Formulation 201 (water-based resin composition) - Acrylic resin (ZB-015M, manufactured by Fujifilm Fine Chemicals Co., Ltd., copolymer resin of methacrylic acid / allyl methacrylate, weight-average molecular weight 25,000, composition ratio (molar ratio) = 20 / 80, solid content 5.00%, aqueous ammonia solution): 4.92 parts Polyfunctional ethylenically unsaturated compound having a carboxylic acid group (Aronix TO-2349, manufactured by Toagosei Co., Ltd.): 0.04 parts ZrO2 particles (Nanouse OZ-S30M, solid content 30.5%, methanol 69.5%, refractive index 2.2, average particle size: approximately 12 nm, manufactured by Nissan Chemical Industries, Ltd.): 4.34 parts Rust inhibitor (benzotriazole derivative, BT-LX, manufactured by Johoku Chemical Industry Co., Ltd.): 0.03 parts Surfactant (fluorosurfactant, Megafac F444, manufactured by DIC Corporation): 0.01 part Distilled water: 24.83 parts Methanol: 65.83 parts

[0206] <<Protective film formation>> The laminate obtained as described above had a photosensitive layer and a second resin layer placed directly on the photosensitive layer on a temporary support, in that order.A 16 μm thick polyethylene terephthalate film (protective film, 16QS62 (16KS40) (manufactured by Toray Industries, Inc.)) was then pressed onto the second resin layer to produce the photosensitive transfer material (transfer film) of Example 1.

[0207] <Evaluation method> The obtained photosensitive transfer material was evaluated as follows.

[0208] <Evaluation of rust prevention> After peeling off the protective film, the photosensitive transfer material was laminated onto one side of a copper plate under the conditions of a laminator temperature of 110°C, a linear pressure of 3 N / cm, and a conveying speed of 2 m / min. Thereafter, the obtained unexposed laminate was exposed to light using a proximity exposure machine (manufactured by Hitachi High-Tech Electronics Engineering Co., Ltd.) equipped with an ultra-high pressure mercury lamp, with the distance between the surface of an exposure mask (a quartz exposure mask having a pattern for forming an overcoat, 1 mm line and space: 5 lines) and the temporary support set to 125 μm, at an exposure dose of 100 mJ / cm through the temporary support. 2 The copper substrate was then subjected to pattern exposure using i-line radiation. After peeling off the temporary support, the laminated body after pattern exposure was washed with a 2% aqueous solution of sodium carbonate at 32°C for 60 seconds. After the washing process, ultrapure water was sprayed onto the copper substrate from an ultra-high pressure cleaning nozzle to remove residues. Subsequently, air was blown onto the copper substrate to remove moisture, and the substrate was post-baked at 140°C for 30 minutes. Thereafter, the patterned sample was left standing in an environment of 85°C and 85% RH for 24 hours. The copper in the space areas of this pattern was visually inspected for discoloration. In the following evaluation criteria, A represents the best rust prevention property and E represents the worst. Any of A, B and C is preferred, A or B is more preferred, and A is particularly preferred. A: The color is the same as the copper before treatment, and there is no discoloration at all. B: Slight red discoloration C: Red discoloration D: Blue discoloration E: Very blue discoloration

[0209] <Rust prevention area> In the evaluation of rust prevention, the vicinity of a portion on the copper plate 1 mm away from the cured film of the photosensitive resin composition was visually observed, and the range of the effect of ratings A to C in the evaluation criteria for rust prevention was evaluated according to the following criteria. In the following evaluation criteria, A is preferable. A: The anti-rust effect is observed even in areas more than 1 mm away from the cured film. B: The rust-preventive effect is only observed in areas less than 1 mm away from the cured film.

[0210] <Evaluation of development residue suppression> After peeling off the protective film, the photosensitive transfer material was laminated onto one side of a copper plate under the conditions of a laminator temperature of 110°C, a linear pressure of 3 N / cm, and a conveying speed of 2 m / min. Thereafter, the obtained unexposed laminate was exposed to light using a proximity exposure machine (manufactured by Hitachi High-Tech Electronics Engineering Co., Ltd.) equipped with an ultra-high pressure mercury lamp, with the distance between the surface of an exposure mask (a quartz exposure mask having a pattern for forming an overcoat, 1 mm line and space: 5 lines) and the temporary support set to 125 μm, at an exposure dose of 100 mJ / cm through the temporary support. 2 The pattern was exposed to i-line radiation. After peeling off the temporary support, the laminate after pattern exposure was immersed in a 1% aqueous solution of sodium carbonate at 23°C and left to stand for 45 seconds for development treatment. Thereafter, it was left to stand in pure water at 23°C for 25 seconds for cleaning treatment. Air was blown onto the copper substrate after cleaning treatment to remove water droplets, and a sample for evaluating development residue suppression was obtained. Residues on the copper in the space portions of this pattern were visually confirmed. In the following evaluation criteria, A indicates the best suppression of development residues, and E indicates the worst. The better the evaluation, the more preferable it is. A: There is no discoloration of the copper, and no deposits on the copper are observed. B: The copper is slightly reddish and no deposits are visible on the copper. C: The copper is slightly reddish and no deposits are visible on the copper. D: The copper is slightly reddish and sparse deposits can be seen on the copper. E: The copper is slightly reddish and deposits on the copper can be seen on the front.

[0211] <Evaluation of substrate adhesion (adhesion)> A copper substrate was used as the support, and the protective film of the transfer film was peeled off onto the copper substrate, and the exposed surface of the second resin layer was closely adhered and laminated to form a laminate A having a layer structure of temporary support / photosensitive layer / second resin layer / copper substrate. The lamination conditions were a laminar temperature of 110°C, a linear pressure of 3 N / cm, and a conveying speed of 2 m / min. The prepared laminate A was exposed to light at a dose of 100 mJ / cm through a temporary support using a proximity exposure machine equipped with an ultra-high pressure mercury lamp (manufactured by Hitachi High-Tech Electronics Engineering Co., Ltd.). 2 After the exposure, the temporary support was peeled off. After the temporary support was peeled off, the exposure dose was further increased to 375 mJ / cm 2 The film was then post-exposed to i-rays and post-baked at 145° C. for 30 minutes to prepare a sample for evaluation. Using the above evaluation sample, a cross-cut test was carried out on a laminate in which 10×10 lattice-shaped cuts were made in accordance with JIS standard (K5400). Specifically, a cutter knife was used to make 1 mm × 1 mm square grid-like cuts in the laminate from the surface of the cured film of the photosensitive layer to the second resin layer, and transparent adhesive tape #600 (manufactured by 3M Japan Ltd.) was pressed and bonded to the surface of the cured film of the photosensitive layer. One end of the bonded transparent adhesive tape was then gripped and pulled in the 180° direction along the surface of the cured film of the photosensitive layer to peel off the transparent adhesive tape. Thereafter, the condition of the surface (peeling surface) of the cured film of the photosensitive layer was visually observed, and the area of ​​the peeled portion was determined and the ratio to the total area of ​​the area with the grid-shaped cuts was calculated. Based on the calculated value, evaluation was performed according to the following evaluation criteria. Of the evaluation criteria, A is the best and E is the worst. -Evaluation criteria- A: The cured film of the photosensitive layer and the second resin layer remain in close contact with each other over 100% of the total area. B: The cured film of the photosensitive layer and the second resin layer remain in close contact with each other over 95% or more and less than 100% of the total area. C: The cured film of the photosensitive layer and the second resin layer remain in close contact with each other over 65% or more and less than 95% of the total area. D: The cured film of the photosensitive layer and the second resin layer remain in close contact with each other in an area of ​​35% or more and less than 65% of the total area. E: The remaining portion of the cured photosensitive layer and the second resin layer in close contact with each other accounts for less than 35% of the total area.

[0212] <Measurement of storage modulus> The storage modulus of the photosensitive resin composition at 100° C. was measured by the following method. The storage modulus was measured using a rheometer (Discovery HR-2) manufactured by TA Instruments, Inc. A parallel plate with a diameter of 20 mm was used as a jig for fixing the sample. The photosensitive layer coating solution was applied onto a 16 μm-thick polyethylene terephthalate film (temporary support, 16QS62 (16KS40) (Toray Industries, Inc.)) using a slit nozzle, adjusted so that the dried thickness would be 10 μm, and the coating was dried in a hot air convection dryer with a temperature gradient of 75°C to 120°C to remove the solvent, forming a photosensitive layer. This was laminated 50 times to obtain a sample with a film thickness of approximately 500 μm. The prepared sample was placed between the plates and pressed tightly against the plates. Dynamic viscoelasticity was measured in shear mode, at a frequency of 1.0 Hz and a strain of 0.5%, in the temperature range of 20 to 125°C, at a heating rate of 5°C / min, and the storage modulus G' (Pa) at 100°C was calculated.

[0213] (Examples 2 to 40 and Comparative Examples 1 to 5) Photosensitive resin compositions and transfer films were prepared in the same manner as in Example 1, except that the types and contents (solid content) of each component other than the solvent were changed as shown in Tables 1 to 4. Further, the obtained photosensitive transfer material was used to carry out various evaluations in the same manner as in Example 1.

[0214] (Examples 41 to 44) The type and content (solid content) of each component other than the solvent were changed as shown in Table 4, and in Examples 41 and 43, the coating liquid for the second resin layer was prepared according to the following formulation 202, and in Examples 42 and 44, the coating liquid for the second resin layer was prepared according to the following formulation 203. Except for this, the photosensitive resin compositions and transfer films were each prepared in the same manner as in Example 1. Further, the obtained photosensitive transfer material was used to carry out various evaluations in the same manner as in Example 1.

[0215] Formulations 202 and 203 for preparing the coating liquid for the second resin layer are shown below.

[0216] - Coating liquid for second resin layer: Formulation 202 (water-based resin composition) - Acrylic resin (ZB-015M, manufactured by Fujifilm Fine Chemicals Co., Ltd., copolymer resin of methacrylic acid / allyl methacrylate, weight-average molecular weight 25,000, composition ratio (molar ratio) = 20 / 80, solid content 5.00%, aqueous ammonia solution): 4.92 parts Polyfunctional ethylenically unsaturated compound having a carboxylic acid group (Aronix TO-2349, manufactured by Toagosei Co., Ltd.): 0.04 parts ZrO2 particles (Nanouse OZ-S30M, solid content 30.5%, methanol 69.5%, refractive index 2.2, average particle size: approximately 12 nm, manufactured by Nissan Chemical Industries, Ltd.): 4.34 parts Additive (adenine, manufactured by Tokyo Chemical Industry Co., Ltd.): 0.03 parts Additive (N-methyldiethanolamine, manufactured by Tokyo Chemical Industry Co., Ltd.): 0.03 parts Surfactant (fluorosurfactant, Megafac F444, manufactured by DIC Corporation): 0.01 part Distilled water: 24.83 parts Methanol: 65.83 parts

[0217] - Coating liquid for second resin layer: Formulation 203 (water-based resin composition) - Acrylic resin (ZB-015M, manufactured by Fujifilm Fine Chemicals Co., Ltd., copolymer resin of methacrylic acid / allyl methacrylate, weight-average molecular weight 25,000, composition ratio (molar ratio) = 20 / 80, solid content 5.00%, aqueous ammonia solution): 4.92 parts Polyfunctional ethylenically unsaturated compound having a carboxylic acid group (Aronix TO-2349, manufactured by Toagosei Co., Ltd.): 0.04 parts ZrO2 particles (Nanouse OZ-S30M, solid content 30.5%, methanol 69.5%, refractive index 2.2, average particle size: approximately 12 nm, manufactured by Nissan Chemical Industries, Ltd.): 4.34 parts Additive (pyrimidine, manufactured by Tokyo Chemical Industry Co., Ltd.): 0.03 parts Additive (N-methyldiethanolamine, manufactured by Tokyo Chemical Industry Co., Ltd.): 0.03 parts Surfactant (fluorosurfactant, Megafac F444, manufactured by DIC Corporation): 0.01 part Distilled water: 24.83 parts Methanol: 65.83 parts (Examples 45 to 48) The type and content (solid content) of each component other than the solvent were changed as shown in Table 5, so that the dried thickness of the photosensitive layer was changed to 5.5 μm, and the coating liquid for the second resin layer was prepared according to the following formulation 204, and the second resin layer was formed as follows. Except for these changes, the photosensitive resin composition and the transfer film were each prepared in the same manner as in Example 1. Further, the obtained photosensitive transfer material was used to carry out various evaluations in the same manner as in Example 1. - Coating liquid for second resin layer: Formulation 204 (water-based resin composition) - Binder polymer Methacrylic acid / allyl methacrylate copolymer resin (Mw: 38,000, composition ratio (molar ratio) = 20 / 80): 12.85 parts Alfon UC-3920 (manufactured by Toagosei Co., Ltd.): 0.47 parts Polyfunctional ethylenically unsaturated compound having a carboxylic acid group (Aronix TO-2349, manufactured by Toagosei Co., Ltd.): 2.00 parts ZrO2 particles (Nanouse OZ-S30M, refractive index 2.2, average particle size: approximately 12 nm, manufactured by Nissan Chemical Industries, Ltd.): 80.00 parts Additive 1 (N-methyldiethanolamine): 2.00 parts Additive 2 (adenine): 2.00 parts Surfactant (fluorosurfactant, Megafac F444, manufactured by DIC Corporation): 0.68 parts Solvent: A mixed solvent of methanol and distilled water in a mass ratio of 7:3 was added so that the solid content concentration of the coating liquid for the second resin layer became 1.66 mass %. <<Formation of second resin layer>> A second resin layer coating solution consisting of formulation 204 was applied onto the photosensitive layer using a slit nozzle, adjusted to a dry thickness of 73 nm, and dried in a hot air convection dryer with a temperature gradient of 40°C to 95°C to remove the solvent, forming a second resin layer disposed in direct contact with the photosensitive layer. The refractive index of the second resin layer was 1.68 at a wavelength of 550 nm at 25°C. Here, formulation 204 was prepared using a resin having an acid group and an aqueous ammonia solution, and the resin having an acid group was neutralized with the aqueous ammonia solution to prepare a coating liquid for a second resin layer, which was an aqueous resin composition containing an ammonium salt of the resin having an acid group. Example 49 The type and content (solid content) of each component other than the solvent were changed as shown in Table 5, so that the thickness of the photosensitive layer after drying was changed to 3.5 μm, and the coating liquid for the second resin layer was prepared according to formulation 204 to form the second resin layer. Except for this, the photosensitive resin composition and the transfer film were each prepared in the same manner as in Example 1. Further, the obtained photosensitive transfer material was used to carry out various evaluations in the same manner as in Example 1. Example 50 The type and content (solid content) of each component other than the solvent were changed as shown in Table 5, so that the thickness of the photosensitive layer after drying was changed to 6.5 μm, and the coating liquid for the second resin layer was prepared according to formulation 204 to form the second resin layer. Except for this, the photosensitive resin composition and the transfer film were each prepared in the same manner as in Example 1. Further, the obtained photosensitive transfer material was used to carry out various evaluations in the same manner as in Example 1.

[0218] The evaluation results are summarized in Tables 1 to 5.

[0219] [Table 1]

[0220] [Table 2]

[0221] [Table 3]

[0222] [Table 4] [Table 5]

[0223] The storage modulus P in Tables 1 to 5 is the storage modulus (unit: 10 2 Pa). In addition, all compounds used as Compound A in the examples are manufactured by Tokyo Chemical Industry Co., Ltd. The abbreviations used in Tables 1 to 5 other than those mentioned above are as follows. M-2: Dipentaerythritol hexaacrylate (A-DPH, manufactured by Shin-Nakamura Chemical Co., Ltd.) M-5: Urethane acrylate 8UX-015A (manufactured by Taisei Fine Chemical Co., Ltd.) DPHA: Dipentaerythritol hexaacrylate (manufactured by Toshin Yushi Co., Ltd.) P-2: Resin shown below (the ratio of each structural unit is a molar ratio), Mw=29,000

[0224] [ka] P-3: Resin shown below Styrene-derived structural unit (St) / methacrylic acid-derived structural unit (MAA) / structural unit obtained by adding glycidyl methacrylate to a methacrylic acid-derived structural unit (GMA-MAA) / methyl methacrylate = 55.1 / 26.5 / 16.85 / 1.6 (mol%), Mw = 17,000 TIFF2025000704000019.tif4096

[0225] D-3: 1-[4-(phenylthio)phenyl]-1,2-octanedione-2-(O-benzoyloxime) (IRGACURE OXE-01, manufactured by BASF) D-4: [8-[5-(2,4,6-trimethylphenyl)-11-(2-ethylhexyl)-11H-benzo[a]carbazolyl][2-(2,2,3,3-tetrafluoropropoxy)phenyl]methanone-(O-acetyloxime) (IRGACURE OXE-03, manufactured by BASF) D-5: 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (IRGACURE 379EG, manufactured by BASF) D-6:1-(biphenyl-4-yl)-2-methyl-2-morpholinopropan-1-one (APi 307, manufactured by Shenzhen UV-ChemTech LTD) E-1: Karenz AOI-BM (photopolymerizable blocked isocyanate compound, 2-(O-[1'-methylpropylideneamino]carboxyamino)ethyl acrylate, manufactured by Showa Denko K.K.) E-2: Karenz MOI-BM (photopolymerizable blocked isocyanate compound, 2-(O-[1'-methylpropylideneamino]carboxyamino)ethyl methacrylate, manufactured by Showa Denko K.K.) E-4: Compound of the following structure TIFF2025000704000020.tif27105

[0226] The results shown in Tables 1 to 5 show that the photosensitive resin compositions of Examples 1 to 50, which are photosensitive resin compositions according to the present disclosure, are superior in suppressing development residues and in preventing rust on exposed wiring around the film after heat treatment of the resulting film or cured film, compared to the photosensitive resin compositions of Comparative Examples 1 to 5. Furthermore, the results shown in Tables 1 to 5 show that the photosensitive resin compositions of Examples 1 to 50, which are curable compositions according to the present disclosure, have a wide range in which the above-mentioned rust prevention effect can be obtained, and also have excellent adhesion to substrates.

[0227] Example 101 A photosensitive resin composition and a photosensitive transfer film were prepared and evaluated in the same manner as in Example 1, except that the second resin layer was not formed. The evaluation results were the same as in Example 1.

[0228] (Examples 102 to 150) Photosensitive resin compositions and photosensitive transfer films were each produced in the same manner as in Example 101, except that the type and content (solid content) of each component was changed as described in Examples 2 to 50 in Tables 1 to 5. The evaluation results were the same as those of Examples 2 to 50.

[0229] (Examples 201A to 201D) In Example 1, except that the temporary support and protective film were changed as shown in Table 6, a transfer film and a laminate were prepared in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The evaluation results were all the same as in Example 1. [Table 6] (Examples 202 to 250) The same changes to the temporary support and protective film as in Examples 201A to 201D for Example 1 were made in Examples 2 to 50, and transfer films and laminates were prepared and evaluated in the same manner as in Example 1. In all cases, the evaluation results were the same as those of the examples before the temporary support and protective film were changed. (Examples 301 to 350) <Preparation of transparent laminate> A substrate was prepared in which a second refractive index adjusting layer, an ITO transparent electrode pattern, and copper wiring were formed on a cycloolefin transparent film. Using the transfer films of Examples 1 to 50 (corresponding to Examples 301 to 350, respectively) from which the protective films had been peeled off, the second refractive index-adjusting layer, the ITO transparent electrode pattern, and the copper wiring were laminated at positions covered by the transfer film. The lamination was performed using a vacuum laminator manufactured by MCK Corporation under the following conditions: cycloolefin transparent film temperature: 40°C, rubber roller temperature: 100°C, linear pressure: 3 N / cm, and conveying speed: 2 m / min. Thereafter, a proximity exposure machine (manufactured by Hitachi High-Tech Electronics Engineering Co., Ltd.) equipped with an ultra-high pressure mercury lamp was used to bring the exposure mask (a quartz exposure mask having a pattern for forming an overcoat) into close contact with the temporary support, and an exposure dose of 100 mJ / cm 2 was applied through the temporary support. 2 The pattern was exposed to i-line radiation. After peeling off the temporary support, the film was developed with a 1% aqueous solution of sodium carbonate at 33° C. for 45 seconds. After that, the residue was removed by spraying ultrapure water from an ultra-high pressure cleaning nozzle onto the developed transparent film substrate. Subsequently, air was blown onto the transparent film substrate to remove moisture, and the substrate was post-baked at 145°C for 30 minutes to form a transparent laminate in which the second refractive index adjustment layer, the ITO transparent electrode pattern, the copper wiring, the first refractive index adjustment layer, and the cured film were laminated in this order on the transparent film substrate. Using the produced transparent laminate, a capacitive touch panel was manufactured by a known method. The produced touch panel was attached to a liquid crystal display element produced by the method described in paragraphs 0097 to 0119 of JP-A No. 2009-47936, thereby producing a liquid crystal display device equipped with a touch panel. It was confirmed that the LCD device equipped with a touch panel had excellent display characteristics and operated without any problems. [Explanation of symbols]

[0230] 10: Transfer film 12: Temporary support 16: Protective film 18, 18A: Photosensitive layer (electrode protective film for touch panel) 20, 20A: Second resin layer (first refractive index adjusting layer) 30: Touch panel 32: Circuit board 34: Transparent electrode pattern 36: Second refractive index adjusting layer 40: First region where transparent electrode pattern exists 42: Second region where no transparent electrode pattern exists 56: Wiring 70: First transparent electrode pattern 72: Second transparent electrode pattern 74: Image display area 75: Image hidden area 90: Touch panel

Claims

1. A pyridine ring structure and one -COOH or one -CONH functional group. 2 A compound A having at least Alkali-soluble binder polymers (excluding polyimide precursors), Ethylenically unsaturated compounds, and A photopolymerization initiator; The ethylenically unsaturated compound includes a di- or higher functional (meth)acrylate compound having an acid group. A photosensitive resin composition (however, the photosensitive resin composition does not contain conductive particles).

2. A pyridine ring structure and one -COOH or one -CONH functional group. 2 A compound A having at least Alkali-soluble binder polymers (excluding polyimide precursors), Ethylenically unsaturated compounds, and A photopolymerization initiator; The ethylenically unsaturated compound includes at least one selected from the group consisting of difunctional or higher functional (meth)acrylate compounds having a carboxy group and carboxylic acid anhydrides thereof. A photosensitive resin composition (however, the photosensitive resin composition does not contain conductive particles).

3. A pyridine ring structure and one -COOH or one -CONH functional group. 2 A compound A having at least Alkali-soluble binder polymers (excluding polyimide precursors), Ethylenically unsaturated compounds, and A photopolymerization initiator; the ethylenically unsaturated compound is a di- or higher functional (meth)acrylate compound, The photopolymerization initiator includes an oxime-based photopolymerization initiator and an α-aminoalkylphenone-based photopolymerization initiator. A photosensitive resin composition (however, the photosensitive resin composition does not contain conductive particles).

4. 4. The photosensitive resin composition according to claim 1, wherein in the compound A, the functional group is a group directly bonded to the pyridine ring.

5. The photosensitive resin composition according to any one of claims 1 to 4, wherein the content of the compound A is 0.1 mass% to 2.0 mass% based on the total solid content of the photosensitive resin composition.

6. 6. The photosensitive resin composition according to claim 1, wherein the alkali-soluble binder polymer is a styrene-acrylic copolymer.

7. The photosensitive resin composition according to any one of claims 1 to 6, which is a photosensitive resin composition for forming a protective film in a touch panel.

8. A temporary support; and a photosensitive layer formed of the photosensitive resin composition according to any one of claims 1 to 7 or obtained by drying the photosensitive resin composition. Transfer film.

9. A cured film obtained by curing the photosensitive resin composition according to any one of claims 1 to 7.

10. A substrate, and A cured film obtained by curing the photosensitive resin composition according to any one of claims 1 to 7. Laminate.

11. Preparing a touch panel substrate having a structure in which at least one of a touch panel electrode and a touch panel wiring is disposed on a substrate; forming a photosensitive layer made of the photosensitive resin composition according to any one of claims 1 to 7 or obtained by drying the photosensitive resin composition on a surface of the touch panel substrate on which at least one of the touch panel electrode and the touch panel wiring is disposed; exposing the photosensitive layer formed on the touch panel substrate to a pattern; and developing the pattern-exposed photosensitive layer to obtain a protective film that protects at least a part of at least one of the touch panel electrode and the touch panel wiring. A method for manufacturing a touch panel.

Citation Information

Patent Citations

  • Photosensitive resin composition

    JP1976148784A

  • Curable resin composition, cured film for display element, method for forming the same, and display element

    JP2016160393A

  • Photosensitive resin composition, photosensitive resin laminate, production method of resin pattern, production method of cured film pattern, and display device

    JP2018072789A

  • Surface coated metal material

    JP2002086613A